Resin composition
A resin composition with a thermosetting resin, inorganic filler, and oligophenylene ether skeleton addresses the trade-off between bendability, insulation reliability, and heat resistance, achieving a cured product with improved mechanical and electrical properties for flexible semiconductor packaging substrates.
Patent Information
- Application Number
- CN202410775283.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-20
- Filing Date
- 2024-06-17
- Publication Date
- 2024-12-20
AI Technical Summary
Existing resin compositions for bendable semiconductor packaging substrates face a trade-off between bendability, insulation reliability, and heat resistance, with flexible resins compromising on either insulation reliability or heat resistance.
A resin composition comprising a thermosetting resin, an inorganic filler, and a resin with an oligophenylene ether skeleton, which exhibits a dielectric loss tangent of less than 0.01, elongation of 5% to 50%, and 200 or more folding times, achieving good folding resistance, insulation reliability, and heat resistance.
The resin composition provides a cured product with excellent folding resistance, insulation reliability, and heat resistance, suitable for high-speed communications and flexible substrates, reducing transmission loss and ensuring substrate adhesion after reflow soldering.
Smart Images

Figure BDA0004895416200000121 
Figure BDA0004895416200000141 
Figure BDA0004895416200000151
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition and also to a resin sheet, a cured product, a flexible substrate and a semiconductor device. Background Art
[0002] With the development of various semiconductor packaging structures in recent years, the demand for interlayer insulating materials for bendable semiconductor packaging substrates, high-speed communications or high multilayering has also increased, and the necessity for low dielectric loss tangent and insulation reliability or heat resistance (close adhesion with conductors after reflow soldering) of insulating materials has also further increased.
[0003] Conventionally, in order to ensure bendability, an insulating material made of a flexible resin has been used (for example, Patent Document 1).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent document 1: Japanese Patent Application Publication No. 2020-21851. Summary of the invention
[0007] Problems to be solved by the invention
[0008] On the other hand, if the flexible resin is mixed to a degree that can ensure the bendability (bending resistance), there is a problem that the insulation material will be poor in reliability or heat resistance. That is, the bendability and insulation reliability and heat resistance are in a trade-off relationship.
[0009] An object of the present invention is to provide a resin composition that can provide a cured product that exhibits good folding resistance and insulation reliability and also has good heat resistance properties (adhesion to the substrate after reflow).
[0010] Means for solving problems
[0011] The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved by a resin composition having the following structure, wherein the resin composition comprises a thermosetting resin, an inorganic filler and a specific resin containing an oligophenylene ether skeleton (hereinafter also referred to as "resin containing an oligophenylene ether skeleton") and exhibits specific physical properties after curing, thereby completing the present invention.
[0012] That is, the present invention includes the following contents.
[0013] [1] A resin composition comprising a thermosetting resin, an inorganic filler, and a resin X having an oligophenylene ether skeleton and having a glass transition temperature of 25° C. or less,
[0014] The cured product of the resin composition exhibits a dielectric loss tangent Df of less than 0.01 and satisfies at least one of the following conditions (1) and (2):
[0015] (1) The elongation is 5% or more and less than 50%;
[0016] (2) The number of folding times in the MIT folding test is 200 times or more.
[0017] [2] The resin composition according to [1], wherein the content of the resin X is 20% by mass or more and less than 85% by mass, based on 100% by mass of the resin component in the resin composition.
[0018] [3] The resin composition according to [1] or [2], wherein the content of the inorganic filler is 50% by mass or less when the non-volatile component in the resin composition is 100% by mass.
[0019] [4] The resin composition according to any one of [1] to [3], wherein the resin X comprises one or more structural units selected from the group consisting of a polyolefin structural unit, a polycarbonate structural unit, a polyether structural unit, a polyester structural unit, a poly(meth)acrylic acid structural unit, and a polysiloxane structural unit.
[0020] [5] The resin composition according to any one of [1] to [4], wherein the resin X contains a cyclic imide structure.
[0021] [6] The resin composition according to any one of [1] to [5], which is used for forming an insulating layer of a flexible substrate.
[0022] [7] A cured product of the resin composition according to any one of [1] to [6].
[0023] [8] A resin sheet comprising: a support and a layer of the resin composition according to any one of [1] to [6] provided on the support.
[0024] [9] The resin sheet described in [8], wherein the support is a thermoplastic resin film or a metal foil.
[0025]
[10] A flexible substrate comprising an insulating layer formed of a cured product of the resin composition according to any one of [1] to [6].
[0026]
[11] A semiconductor device comprising the flexible substrate described in
[10] .
[0027] Effects of the Invention
[0028] According to the present invention, there is provided a novel resin composition capable of providing a cured product that exhibits excellent folding resistance and insulation reliability and also has excellent heat resistance characteristics (adhesion to the substrate after reflow). DETAILED DESCRIPTION
[0029] <Explanation of terms>
[0030] In the present specification, the term "may have a substituent" with respect to a compound or a group refers to the following two cases: a case where hydrogen atoms of the compound or group are not substituted by a substituent, and a case where a part or all of hydrogen atoms of the compound or group are substituted by a substituent.
[0031] In the present specification, the term "substituent" means a halogen atom, an alkyl group, an alkenyl group, a cycloalkyl group, an alkoxy group, a cycloalkyloxy group, an aryl group, an aryloxy group, an aralkyl group, an aralkyloxy group, a monovalent heterocyclic group, an alkylidene group, an amino group, a silyl group, a carboxyl group, a sulfo group, a cyano group, a nitro group, a hydroxyl group, a mercapto group, and an oxo group, unless otherwise specified.
[0032] Examples of the halogen atom used as a substituent include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. The alkyl group used as a substituent may be either linear or branched. The number of carbon atoms of the alkyl group is preferably 1 to 12, more preferably 1 to 6, and further preferably 1 to 3. The alkenyl group used as a substituent may be either linear or branched. The number of carbon atoms of the alkenyl group is preferably 2 to 12, more preferably 2 to 6, and further preferably 2 or 3. The number of carbon atoms of the cycloalkyl group used as a substituent is preferably 3 to 12, and further preferably 3 to 6. The alkoxy group used as a substituent may be either linear or branched. The number of carbon atoms of the alkoxy group is preferably 1 to 12, and further preferably 1 to 6. The number of carbon atoms of the cycloalkoxy group used as a substituent is preferably 3 to 12, and further preferably 3 to 6. The aryl group used as a substituent is a group obtained by removing one hydrogen atom from an aromatic ring of an aromatic hydrocarbon. The number of carbon atoms of the aryl group used as a substituent is preferably 6 to 14, and further preferably 6 to 10. The number of carbon atoms of the aryloxy group used as a substituent is preferably 6 to 14, more preferably 6 to 10. The number of carbon atoms of the aralkyl group used as a substituent is preferably 7 to 15, more preferably 7 to 11. The number of carbon atoms of the aralkyloxy group used as a substituent is preferably 7 to 15, more preferably 7 to 11. The monovalent heterocyclic group used as a substituent refers to a group obtained by removing one hydrogen atom from the heterocyclic ring of a heterocyclic compound. The number of carbon atoms of the monovalent heterocyclic group is preferably 3 to 15, more preferably 3 to 9. The alkylene group used as a substituent refers to a group obtained by removing two hydrogen atoms from the same carbon atom of an alkane. The number of carbon atoms of the alkylene group is preferably 1 to 12, more preferably 1 to 6, and even more preferably 1 to 3. The above-mentioned substituent may further have a substituent (hereinafter, sometimes also referred to as a "secondary substituent"). As the secondary substituent, the same substituent as the above-mentioned substituent can be used unless otherwise specified.
[0033] The present invention will be described in detail below by showing embodiments and examples, but the present invention is not limited to the following embodiments and examples, and can be implemented with any changes within the scope of the claims of the present invention and their equivalents.
[0034] [Resin composition]
[0035] The resin composition of the present invention is characterized in that it is a resin composition comprising a thermosetting resin, an inorganic filler, and a resin X having an oligophenylene ether skeleton and having a glass transition temperature of 25° C. or less, wherein a cured product of the resin composition exhibits a dielectric loss tangent Df of less than 0.01 and satisfies at least one of the following conditions (1) and (2):
[0036] (1) The elongation is 5% or more and less than 50%;
[0037] (2) The number of folding times in the MIT folding test is 200 times or more.
[0038] As described above, the demand for high-speed communication or high multilayering has also increased for interlayer insulating materials of bendable semiconductor packaging substrates, and the necessity for good dielectric properties (low dielectric loss tangent), insulation reliability, and heat resistance (substrate adhesion after reflow soldering) has also increased. In this regard, if a flexible resin is mixed to a degree that can ensure bendability (folding resistance), there will be a problem of insulating materials with poor reliability or heat resistance. That is, bendability is in a compromise relationship with insulation reliability and heat resistance.
[0039] In contrast, the resin composition of the present invention can provide a cured product that exhibits good folding resistance and insulation reliability and also has good heat resistance (substrate adhesion after reflow soldering), wherein the resin composition contains a resin X containing an oligophenylene ether skeleton having a glass transition temperature of 25°C or less in combination with a thermosetting resin and an inorganic filler, exhibits a dielectric loss tangent Df of less than 0.01 after curing, and satisfies conditions related to specific mechanical properties. In this way, the resin composition of the present invention can advantageously achieve a reduction in transmission loss when operating in a high-frequency environment required for next-generation high-speed communications, and significantly contributes to the realization of a flexible substrate that satisfies both insulation reliability and heat resistance.
[0040] Hereinafter, each component will be described.
[0041] <Thermosetting resin>
[0042] The resin composition of the present invention contains a thermosetting resin.
[0043] The thermosetting resin is not particularly limited, and examples thereof include epoxy resins, benzocyclobutene resins, epoxy acrylate resins, urethane acrylate resins, urethane resins, cyanate resins, polyimide resins, benzocyclobutene resins, epoxy acrylate resins, urethane acrylate resins, urethane resins, cyanate resins, polyimide resins, Oxazine resin, unsaturated polyester resin, melamine resin, silicone resin, etc. Among them, in the combination of the inorganic filler and the resin X containing the oligophenylene ether skeleton described later, it is preferred to include an epoxy resin from the viewpoint of producing a cured product having good folding resistance and insulation reliability and good heat resistance (substrate adhesion after reflow soldering).
[0044] As long as the epoxy resin has more than one (preferably more than two) epoxy groups in one molecule, its type is not particularly limited. As the epoxy resin, for example, bisphenol type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol novolac type epoxy resin, phenol novolac type epoxy resin, tert-butyl-catechol type epoxy resin, naphthalene type epoxy resin, naphthol type epoxy resin, anthracene type epoxy resin, glycidyl amine type epoxy resin, glycidyl ester type epoxy resin, cresol novolac type epoxy resin, biphenyl type epoxy resin, linear aliphatic epoxy resin, epoxy resin with butadiene structure, alicyclic epoxy resin, heterocyclic epoxy resin, epoxy resin containing spiro ring, cyclohexane type epoxy resin, cyclohexanedimethanol type epoxy resin, naphthylene ether type epoxy resin, trimethylol type epoxy resin, tetraphenylethane type epoxy resin can be cited. Bisphenol epoxy resin refers to epoxy resin having a bisphenol structure, for example, bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, bisphenol AF epoxy resin. Biphenyl epoxy resin refers to epoxy resin having a biphenyl structure, and the biphenyl structure may have a substituent such as an alkyl group, an alkoxy group, or an aryl group. Therefore, bixylenol epoxy resin and biphenyl aralkyl epoxy resin are also included in biphenyl epoxy resin.
[0045] Epoxy resins can be divided into epoxy resins that are liquid at a temperature of 20°C (hereinafter referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20°C (hereinafter referred to as "solid epoxy resins"), but the resin composition of the present invention may contain only liquid epoxy resins, only solid epoxy resins, or a combination of liquid epoxy resins and solid epoxy resins.
[0046] As the liquid epoxy resin, a liquid epoxy resin having two or more epoxy groups in one molecule is preferred.
[0047] As the liquid epoxy resin, preferred are glycyrrhizin type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexanedimethanol type epoxy resin, cyclic aliphatic glycidyl ether and epoxy resin having a butadiene structure.
[0048] Specific examples of liquid epoxy resins include: "EX-992L" manufactured by Nagase ChemteX; "YX7400" and "YX7400N" manufactured by Mitsubishi Chemical Corporation; "HP4032", "HP4032D" and "HP4032SS" (naphthalene-type epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL", "828EL", "825" and "EPIKOTE828EL" (bisphenol A-type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F-type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152 ” (phenol novolac type epoxy resin); “630”, “630LSD”, “604” (glycidylamine type epoxy resin) manufactured by Mitsubishi Chemical Corporation; “ED-523T” (licorice alcohol type epoxy resin) manufactured by ADEKA; “EP-3950L”, “EP-3980S” (glycidylamine type epoxy resin) manufactured by ADEKA; “EP-4088S” (dicyclopentadiene type epoxy resin) manufactured by ADEKA; “ZX1059” (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel Chemical Materials Co., Ltd.; Nagase "EX-721" (glycidyl ester type epoxy resin) manufactured by ChemteX; "EX-991L" (epoxy resin containing an alkylene oxide skeleton and a butadiene skeleton) manufactured by Nagase ChemteX; "Celloxide 2021P" (alicyclic epoxy resin with an ester skeleton) manufactured by Daicel; "PB-3600" manufactured by Daicel; "JP-100" and "JP-200" (epoxy resins with a butadiene structure) manufactured by Nippon Soda Co., Ltd.; "ZX1658" and "ZX1658GS" (liquid 1,4-glycidyl cyclohexane type epoxy resins) manufactured by Nippon Steel Chemical Materials Co., Ltd.; "EG-280" (epoxy resin containing a fluorene structure) manufactured by Osaka Gas Chemical Co., Ltd.; "EX-201" (cyclic aliphatic glycidyl ether) manufactured by Nagase ChemteX, etc.
[0049] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferred, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferred.
[0050] As solid epoxy resins, preferred are biphenylol-type epoxy resins, naphthalene-type epoxy resins, naphthalene-type tetrafunctional epoxy resins, naphthol novolac-type epoxy resins, cresol novolac-type epoxy resins, dicyclopentadiene-type epoxy resins, trisphenol-type epoxy resins, naphthol-type epoxy resins, biphenyl-type epoxy resins, naphthylene ether-type epoxy resins, anthracene-type epoxy resins, bisphenol A-type epoxy resins, bisphenol AF-type epoxy resins, phenol aralkyl-type epoxy resins, tetraphenylethane-type epoxy resins, and phenol phthalimide-type epoxy resins.
[0051] Specific examples of solid epoxy resins include: "HP4032H" (naphthalene-type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene-type tetrafunctional epoxy resin) manufactured by DIC Corporation; "N-690" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", "HP-7200H", and "HP-7200L" (dicyclopentadiene-type epoxy resin) manufactured by DIC Corporation; "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP-6000", "HP-6000L" (naphthylene ether type epoxy resin); "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC3000H", "NC3000", "NC3000L", "NC3000FH", "NC3100" (biphenyl type epoxy resin) manufactured by Nippon Kayaku Co., Ltd. ); "ESN475V", "ESN4100V" (naphthalene type epoxy resin) manufactured by Nippon Steel Chemicals; "ESN485" (naphthol type epoxy resin) manufactured by Nippon Steel Chemicals; "ESN375" (dihydroxynaphthalene type epoxy resin) manufactured by Nippon Steel Chemicals; "YX4000H", "YX4000", "YX4000HK", "YL7890" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical; "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical; "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical ); "YX7700" (phenol aralkyl type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd.; "YL7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER1010" (bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "WHR991S" (phenol phthalimide type epoxy resin) manufactured by Nippon Kayaku Co., Ltd., etc. These may be used alone or in combination of two or more.
[0052] When a liquid epoxy resin and a solid epoxy resin are used in combination as the epoxy resin, their mass ratio (liquid epoxy resin:solid epoxy resin) is preferably 10:1 to 1:10, more preferably 5:1 to 1:5, further preferably 3:1 to 1:2, and particularly preferably 2:1 to 1:1.
[0053] The epoxy equivalent of the epoxy resin is preferably 50 g / eq. to 5,000 g / eq., more preferably 60 g / eq. to 2,000 g / eq., further preferably 70 g / eq. to 1,000 g / eq., and further preferably 80 g / eq. to 500 g / eq. The epoxy equivalent is the mass of the resin per 1 equivalent of epoxy group. The epoxy equivalent can be measured according to JIS K7236.
[0054] The weight average molecular weight of the epoxy resin is preferably 100 to 5,000, more preferably 250 to 3,000, and even more preferably 400 to 1,500. The weight average molecular weight of the resin can be measured as a polystyrene-equivalent value by gel permeation chromatography (GPC).
[0055] The content of the thermosetting curing resin in the resin composition is not particularly limited. When the resin component in the resin composition is set to 100% by mass, it is preferably 3% by mass or more, more preferably 5% by mass or more, and further preferably 6% by mass or more, 8% by mass or more, or 10% by mass or more. The upper limit of this content is not particularly limited, and can be determined according to the characteristics required by the resin composition, for example, it can be 60% by mass or less, 50% by mass or less, or 40% by mass or less.
[0056] In the present invention, the "resin component" referred to in relation to the resin composition refers to a component obtained by removing the above-mentioned inorganic filler from the non-volatile components constituting the resin composition.
[0057] <Inorganic fillers>
[0058] The resin composition of the present invention contains an inorganic filler. By containing an inorganic filler, the thermal expansion coefficient or dielectric loss tangent can be reduced.
[0059] As inorganic filler, for example, silicon dioxide, aluminum oxide, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum silicate, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate, calcium zirconate, zirconium phosphate and zirconium tungstate phosphate, etc., can be mentioned. Among these, silicon dioxide is particularly suitable. As silicon dioxide, for example, amorphous silicon dioxide, fused silica, crystalline silicon dioxide, synthetic silicon dioxide, hollow silica, etc. can be mentioned. In addition, as silicon dioxide, spherical silicon dioxide is preferred. One inorganic filler can be used alone, or two or more can be used in combination.
[0060] Commercially available products of inorganic fillers include, for example, "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical Materials Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs; "UFP-30", "DAW-03", and "FB-105FD" manufactured by Denka; "SILFIL NSS-3N", "SILFIL NSS-4N", and "SILFIL NSS-5N" manufactured by Tokuyama Co., Ltd.; and "CellSpheres" and "MGH-005" manufactured by Pacific Cement Co., Ltd.
[0061] The average particle size of the inorganic filler is not particularly limited, but is preferably 10 μm or less, more preferably 5 μm or less, further preferably 3 μm or less, 2 μm or less, 1 μm or less, or 0.7 μm or less. The lower limit of the average particle size is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.05 μm or more, further preferably 0.07 μm or more, 0.1 μm or more, or 0.2 μm or more.
[0062] The average particle size of the inorganic filler can be measured by the laser diffraction / scattering method based on Mie scattering theory. Specifically, the particle size distribution of the inorganic filler can be made on a volume basis by a laser diffraction scattering particle size distribution measuring device, and the median particle size is measured as the average particle size. The sample can be measured using a sample obtained by weighing 100 mg of inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing it by ultrasonic waves for 10 minutes. For the sample, a laser diffraction particle size distribution measuring device is used, and the wavelength of the light source is set to blue and red, and the particle size distribution of the volume basis of the inorganic filler is measured in a flow cell (flowcell) manner, and the average particle size as the median particle size is calculated according to the obtained particle size distribution. As a laser diffraction particle size distribution measuring device, for example, "LA-960" manufactured by Horiba Manufacturing Co., Ltd. can be cited.
[0063] The specific surface area of the inorganic filler is not particularly limited, but is preferably 0.1 m 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, 3m 2 / g or above or 5m 2 The upper limit of the specific surface area is not particularly limited, but is preferably 100 m 2 / g or less, more preferably 80m 2 / g or less, more preferably 60m2 / g or less, 50m 2 / g or below or 40m 2 / g or less.
[0064] The specific surface area of the inorganic filler can be obtained by using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountech) according to the BET method, allowing nitrogen to adsorb on the surface of the sample, and calculating the specific surface area by the BET multipoint method.
[0065] The inorganic filler is preferably surface treated with an appropriate surface treatment agent. By performing surface treatment, the moisture resistance and dispersibility of the inorganic filler can be improved. As the surface treatment agent, for example, silane coupling agents such as vinyl silane coupling agent, epoxy silane coupling agent, styrene-based silane coupling agent, (methyl) acrylic silane coupling agent, amino silane coupling agent, isocyanurate silane coupling agent, urea-based silane coupling agent, mercapto-based silane coupling agent, isocyanate silane coupling agent, anhydride silane coupling agent, etc.; non-silane coupling-alkoxysilane compounds such as methyltrimethoxysilane and phenyltrimethoxysilane; silazane compounds, etc. The surface treatment agent can be used alone or in combination of two or more.
[0066] Commercially available products of the surface treatment agent include, for example, "KBM403" (3-glycidoxypropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBM803" (3-mercaptopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBE903" (3-aminopropyltriethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., and "SZ-31" (hexamethyldisilazane) manufactured by Shin-Etsu Chemical Co., Ltd.
[0067] The degree of surface treatment by the surface treatment agent is preferably controlled within a predetermined range from the viewpoint of improving the dispersibility of the inorganic filler. Specifically, 100% by mass of the inorganic filler is preferably surface treated with 0.2% to 5% by mass of the surface treatment agent.
[0068] The degree of surface treatment by the surface treatment agent can be evaluated by the amount of carbon per unit surface area of the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of the inorganic filler is preferably 0.02 mg / m 2 More preferably 0.1 mg / m 2 More preferably 0.2 mg / m 2On the other hand, from the viewpoint of preventing the increase of the melt viscosity of the resin composition or the melt viscosity in the form of a sheet, 1.0 mg / m 2 Below, more preferably 0.8 mg / m 2 Below, more preferably 0.5 mg / m 2 Below. The amount of carbon per unit surface area of the inorganic filler can be measured after the surface-treated inorganic filler is washed with a solvent (for example, methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic washing is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid components, the amount of carbon per unit surface area of the inorganic filler can be measured using a carbon analyzer. As a carbon analyzer, "EMIA-320V" manufactured by Horiba, Ltd., etc. can be used.
[0069] In combination with the resin X, from the viewpoint of producing a cured product that exhibits good folding resistance and insulation reliability and also has good heat resistance (substrate adhesion after reflow soldering), the content of the inorganic filler in the resin composition is preferably 50% by mass or less, more preferably 45% by mass or less, and further preferably 44% by mass or less, 42% by mass or less, or 40% by mass or less, when the non-volatile component in the resin composition is set to 100% by mass. According to the present invention using the resin X containing an oligophenylene ether skeleton described later, the lower limit of the content of the inorganic filler is not particularly limited, and may be, for example, 5% by mass or more, 10% by mass or more, 15% by mass or more, etc.
[0070] <Resin X containing an oligophenylene ether skeleton>
[0071] The resin composition of the present invention contains a resin X having an oligophenylene ether skeleton and having a glass transition temperature of 25° C. or less (also simply referred to as “resin X”).
[0072] Here, the glass transition temperature of the resin X being 25° C. or lower means that if the resin X has only one glass transition temperature, the glass transition temperature is 25° C. or lower, and when the resin X has a plurality of glass transition temperatures, at least one glass transition temperature is 25° C. or lower. By using such a resin X in combination with a thermosetting resin and an inorganic filler, a resin composition that can produce a cured product that exhibits good folding resistance and insulation reliability and also has good heat resistance characteristics (substrate adhesion after reflow soldering) can be achieved.
[0073] -Oligophenylene ether skeleton-
[0074] The resin X preferably comprises an oligophenylene ether skeleton containing a plurality of phenylene ether units represented by the following formula (1).
[0075] [Chemical formula 1]
[0076]
[0077] In formula (1),
[0078] R each independently represents a halogen atom, an alkyl group which may have a substituent, an alkoxy group which may have a substituent, an aryl group which may have a substituent, an amino group which may have a substituent, a nitro group or a carboxyl group,
[0079] m represents an integer of 0-4.
[0080] The alkyl group or alkoxy group in R may be linear or branched, and the number of carbon atoms thereof is preferably 1 to 10, more preferably 1 to 6, and further preferably 1 to 4 or 1 to 3. The number of carbon atoms does not include the number of carbon atoms of the substituent.
[0081] The number of carbon atoms of the aryl group in R is preferably 6 to 14, more preferably 6 to 10. The number of carbon atoms does not include the number of carbon atoms of the substituent.
[0082] The substituents that the monovalent group represented by R may have are as described above, and among them, preferably one or more selected from a halogen atom, an alkyl group, an alkoxy group and an aryl group, more preferably one or more selected from a halogen atom, an alkyl group and an aryl group, and further preferably one or more selected from a fluorine atom, an alkyl group having 1 to 6 carbon atoms and an aryl group having 6 to 10 carbon atoms.
[0083] In formula (1), m represents an integer of 0 to 4, preferably an integer of 0 to 3, and more preferably an integer of 1 to 3.
[0084] In combination with a thermosetting resin and an inorganic filler, from the viewpoint of providing a cured product that exhibits good folding resistance and insulation reliability and also has good heat resistance (substrate adhesion after reflow), the oligophenylene ether skeleton is preferably an oligophenylene ether skeleton containing a plurality of one or more units selected from 2,6-disubstituted-1,4-phenylene ether units, 2,5-disubstituted-1,4-phenylene ether units and 2,3,6-trisubstituted-1,4-phenylene ether units, among which an oligophenylene ether skeleton containing a plurality of 2,6-disubstituted-1,4-phenylene ether units is preferred (herein, the substituents at the 2,6 positions, the substituents at the 2,5 positions and the substituents at the 2,3,6 positions correspond to R in formula (1)).
[0085] Specific examples of suitable oligophenylene ether skeletons include oligo(2,6-dialkyl-1,4-phenylene ether) skeletons, oligo(2-alkyl-6-aryl-1,4-phenylene ether) skeletons, oligo(2,6-diaryl-1,4-phenylene ether) skeletons, oligo(2,6-dihalogenated-1,4-phenylene ether) skeletons, and oligo(2,6-disubstituted-1,4-phenylene ether) skeletons; oligo(2,6-disubstituted phenol) skeletons and other phenol compounds (e.g., 2 The present invention relates to a low-polyphenylene ether skeleton comprising a copolymer structure of 2,5-disubstituted phenols such as 2,5-dialkylphenol, 2-alkyl-5-arylphenol, 2,5-diarylphenol or 2,3,6-trisubstituted phenols such as 2,3,6-trialkylphenol and 2,3,6-trihalogenated phenol, and the like, a coupling reaction product of 2,6-disubstituted phenol and a bisphenol compound (biphenol or bisphenol), and the like containing multiple 2,6-disubstituted-1,4-phenylene ether units.
[0086] In combination with a thermosetting resin and an inorganic filler, the resin X preferably contains a structure represented by the following formula (2) as an oligophenylene ether skeleton from the viewpoint of producing a cured product exhibiting good folding resistance and insulation reliability and also having good heat resistance (substrate adhesion after reflow soldering).
[0087] [Chemical formula 2]
[0088]
[0089] In formula (2),
[0090] R and m have the same meanings as above.
[0091] L represents a divalent linking group,
[0092] n1 and n2 each independently represent an integer of 1 to 100.
[0093] In formula (2), L represents a divalent linking group. Examples of the divalent linking group include a single bond, an alkylene group which may have a substituent, an alkenylene group which may have a substituent, an arylene group which may have a substituent, an alkylarylene group which may have a substituent, a heteroarylene group which may have a substituent, -O-, -NH-, -NR- x -, -CO-, -CS-, -SO-, -SO2-, -C(=O)O-, -NHC(=O)-, -NC(=O)N-, -NHC(=O)O-, -C(=O)-, -S-, and a divalent group composed of a plurality thereof. x It represents a hydrocarbon group having 1 to 12 carbon atoms.
[0094] Among them, from the viewpoint of enjoying the effects of the present invention more, the divalent linking group represented by L is preferably a single bond, an alkylene group which may have a substituent, an alkenylene group which may have a substituent, an arylene group which may have a substituent, -O-, -NR x -, -CO-, -CS-, -SO-, -SO2-, and a divalent group composed of a plurality thereof, more preferably a single bond, an alkylene group which may have a substituent, an arylene group which may have a substituent, and a divalent group composed of a plurality thereof.
[0095] The substituents that the divalent group in L may have are as described above. From the viewpoint of being able to better enjoy the effects of the present invention, it is preferably one or more selected from halogen atoms and hydrocarbon groups, more preferably one or more selected from halogen atoms, alkyl groups and aryl groups, and further preferably one or more selected from fluorine atoms, alkyl groups having 1 to 6 carbon atoms and aryl groups having 6 to 10 carbon atoms.
[0096] The number of carbon atoms of the divalent linking group represented by L is preferably 60 or less, more preferably 48 or less, further preferably 36 or less, and further preferably 24 or less.
[0097] Among them, in combination with a thermosetting resin and an inorganic filler, from the viewpoint of producing a cured product having good folding resistance and insulation reliability and also good heat resistance (substrate adhesion after reflow), the divalent linking group represented by L is preferably an alkylene group having 1 to 6 carbon atoms or a divalent group represented by the following formula (3).
[0098] [Chemical formula 3]
[0099]
[0100] In formula (3),
[0101] R 1 ~R 8 each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a phenyl group,
[0102] * indicates a bond.
[0103] In formula (3), R 1 ~R 8 Each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a phenyl group. 1 , R 2 , R 7 and R 8 Preferably, it is an alkyl group having 1 to 6 carbon atoms, and more preferably, it is an alkyl group having 1 to 4 carbon atoms. 3 and R 4One of them represents a hydrogen atom and the other represents an alkyl group having 1 to 6 carbon atoms, and preferably R 5 and R 6 One of them represents a hydrogen atom, and the other represents an alkyl group having 1 to 6 carbon atoms.
[0104] In formula (2), R and m are as described above for the phenylene ether unit of formula (1). Among them, the phenylene ether unit constituting the oligophenylene ether skeleton represented by formula (2) is preferably a 2,6-disubstituted-1,4-phenylene ether unit, and more preferably a 2,6-dialkyl-1,4-phenylene ether unit, a 2-alkyl-6-aryl-1,4-phenylene ether unit, a 2,6-diaryl-1,4-phenylene ether unit, or a 2,6-dihalogenated-1,4-phenylene ether unit from the viewpoint of being able to enjoy the effects of the present invention.
[0105] In combination with a thermosetting resin and an inorganic filler, from the viewpoint of producing a cured product having good folding resistance and insulation reliability and good heat resistance (adhesion to the substrate after reflow), the resin X preferably contains a structure represented by the following formula (2-1) as an oligophenylene ether skeleton.
[0106] [Chemical formula 4]
[0107]
[0108] In formula (2-1), R, L, n1 and n2 have the same meanings as described above.
[0109] In formula (2-1), R, L, n1 and n2 have the same meanings as above, and suitable examples thereof are also as described above. Among them, from the viewpoint of being able to further enjoy the effects of the present invention,
[0110] R each independently represents preferably a halogen atom, an alkyl group or an aryl group, more preferably a halogen atom, an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms, and further preferably an alkyl group having 1 to 6 carbon atoms.
[0111] L is preferably a single bond, an alkylene group which may have a substituent, an alkenylene group which may have a substituent, an arylene group which may have a substituent, -O-, -NR x -, -CO-, -CS-, -SO-, -SO2-, and a divalent group composed of a plurality of them, more preferably a single bond, an alkylene group which may have a substituent, an arylene group which may have a substituent, and a divalent group composed of a plurality of them, further preferably an alkylene group having 1 to 6 carbon atoms or a divalent group represented by the above formula (3),
[0112] n1 and n2 each independently represent an integer in the range of 1 to 100, and when related to the flexible skeleton described later, preferably represent an integer in the following range: at least one glass transition temperature of the resin X is 25°C or less, more preferably a range that satisfies the suitable conditions (the conditions are described later), and further a range that satisfies the suitable conditions for the weight average molecular weight of the resin X (the conditions are described later).
[0113] -Flexible skeleton-
[0114] The resin X includes, in addition to the oligophenylene ether skeleton which is a rigid skeleton, a skeleton which is more flexible than the oligophenylene ether skeleton (also simply referred to as a "flexible skeleton").
[0115] In combination with a thermosetting resin and an inorganic filler, the resin X preferably contains as a flexible skeleton one or more structural units selected from the group consisting of a polyolefin structural unit, a polycarbonate structural unit, a polyether structural unit, a polyester structural unit, a poly(meth)acrylic acid structural unit, and a polysiloxane structural unit, from the viewpoint of providing a cured product exhibiting better folding resistance and insulation reliability and better heat resistance (substrate adhesion after reflow soldering).
[0116] Examples of the polyolefin structural unit include polyethylene structural units, polypropylene structural units, polybutadiene structural units, hydrogenated polybutadiene structural units, polyisoprene structural units, and hydrogenated polyisoprene structural units. Here, the "hydrogenated polybutadiene structural unit" refers to a unit in which a part or all of the unsaturated bonds of the polybutadiene structural unit are hydrogenated, and similarly, the "hydrogenated polyisoprene structural unit" refers to a unit in which a part or all of the unsaturated bonds of the polyisoprene structural unit are hydrogenated.
[0117] As described later, the polyolefin structural unit may be a residual structural unit obtained by removing two or more hydroxyl groups from a polyol compound containing a polyolefin structure, for example, when a polyol compound having a flexible skeleton (in this embodiment, a polyol compound containing a polyolefin structure) is used to produce the resin X. Commercially available polyol compounds containing a polyolefin structure may be used, and examples of such commercially available products include "G-1000", "G-2000", "G-3000" (polybutadiene containing hydroxyl groups at both ends), "GI-1000", "GI-2000", "GI-3000" (hydrogenated polybutadiene containing hydroxyl groups at both ends) manufactured by Nippon Soda Co., Ltd.
[0118] Examples of the polycarbonate structural unit include aliphatic polycarbonates (polyethylene carbonate, polypropylene carbonate, polybutylene carbonate, polycyclohexane carbonate, etc.) and aromatic polycarbonates (polybisphenol A carbonate, polybisphenol F carbonate, polybisphenol S carbonate, etc.).
[0119] As described later, for example, when a polyol compound having a flexible skeleton (in this embodiment, a polyol compound containing a polycarbonate structure) is used to produce the resin X, the polycarbonate structural unit may be a residual structural unit obtained by removing two or more hydroxyl groups from the polyol compound containing a polycarbonate structure. The polyol compound containing a polycarbonate structure may be a commercially available product, and examples of such commercially available products include: "T6002" and "T6001" (polycarbonates containing hydroxyl groups at both ends) manufactured by Asahi Kasei Corporation; "C-1090", "C-2015N", "C-2090", and "C-3090" (polycarbonates containing hydroxyl groups at both ends) manufactured by Kuraray Corporation.
[0120] Examples of the polyether structural unit include a polyethylene glycol structural unit, a polypropylene glycol structural unit, a polytetramethylene glycol structural unit, and a polybutylene glycol structural unit.
[0121] The polyether structural unit, as described later, may be a residual structural unit obtained by removing two or more hydroxyl groups from a polyol compound containing a polyether structure, for example, when the resin X is produced using a polyol compound having a flexible skeleton (in this embodiment, a polyol compound containing a polyether structure). As the polyol compound containing a polyether structure, commercially available products can be used. Examples of such commercial products include "Pronon #102", "Pronon #104", "Pronon #201", "Pronon #202B", "Pronon #204", "Pronon #208", "UNILUBE 70DP-600B", and "UNILUBE 70DP-950B" (polyethylene glycol-polypropylene glycol copolymers) manufactured by NOF Corporation; and "Pluronic (registered trademark) L-23", "Pluronic L-31", "Pluronic L-44", "Pluronic L-61", "ADEKA Pluronic L-62", "Pluronic L-64", "Pluronic L-71", "Pluronic L-72", "Pluronic L-101", "Pluronic L-121", "Pluronic P-84", "Pluronic P-85", "Pluronic P-103", "Pluronic F-68", and "Pluronic F-69" manufactured by ADEKA Corporation. F-88", "Pluronic F-108", "Pluronic 25R-1", "Pluronic 25R-2", "Pluronic 17R-2", "Pluronic 17R-3", "Pluronic 17R-4" (polyethylene glycol-polypropylene glycol copolymer).
[0122] Examples of the polyester structural unit include a polyethylene terephthalate structural unit, a polybutylene terephthalate structural unit, a polyethylene naphthalate structural unit, a polybutylene naphthalate structural unit, and a polytrimethylene terephthalate structural unit.
[0123] As described later, the polyester structural unit may be a residual structural unit obtained by removing two or more hydroxyl groups from a polyol compound having a polyester structure when a polyol compound having a flexible skeleton (in this embodiment, a polyol compound having a polyester structure) is used to produce the resin X. The polyol compound having a polyester structure may be a commercially available product, and examples of such commercially available products include Vylon (registered trademark) manufactured by Toyobo Co., Ltd., Polyestar (registered trademark) manufactured by Nippon Synthetic Chemical Industry Co., Ltd., and Slack (registered trademark) manufactured by RESONAC Co., Ltd.
[0124] The poly(meth)acrylic acid structural unit refers to a structural unit containing at least one of a plurality of acrylic acid structures and methacrylic acid structures. As described later, for example, when a polyol compound having a flexible skeleton (in this embodiment, a polyol compound containing a poly(meth)acrylic acid structure) is used to produce resin X, the poly(meth)acrylic acid structural unit may be a residual structural unit obtained by removing two or more hydroxyl groups from the polyol compound containing a poly(meth)acrylic acid structure. Commercially available products may be used for the polyol compound containing a poly(meth)acrylic acid structure. Examples of such commercially available products include Teisan Resin "SG-600TEA" and "SG-790" (hydroxyl-containing acrylate copolymer resins) manufactured by Nagase ChemteX Co., Ltd. and "W-197C" (hydroxyl-containing acrylate copolymer resin) manufactured by Negami Industries Co., Ltd.
[0125] As a polysiloxane structural unit, a dialkyl polysiloxane structural unit, a diaryl polysiloxane structural unit, a monoalkyl monoaryl polysiloxane structural unit, and a monoalkyl polysiloxane structural unit are mentioned, for example.
[0126] As described later, the polysiloxane structural unit may be a residual structural unit obtained by removing two or more hydroxyl groups from a polyol compound containing a polysiloxane structure, for example, when a polyol compound having a flexible skeleton (in this embodiment, a polyol compound containing a polysiloxane structure) is used to produce the resin X. A commercially available polyol compound containing a polysiloxane structure may be used, and examples of such commercially available products include "X-21-5841" and "KF-9701" (both terminal hydroxyl polysiloxane) manufactured by Shin-Etsu Chemical Co., Ltd.
[0127] As described above, the resin X comprises an oligophenylene ether skeleton and a flexible skeleton. The mass ratio of the oligophenylene ether skeleton to the flexible skeleton in the resin X (flexible skeleton / oligophenylene ether skeleton) is preferably 0.2 or more, more preferably 0.4 or more, and further preferably 0.5 or more, 0.6 or more, or 0.7 or more, from the viewpoint of bringing about a cured product that can suppress warping, present better dielectric properties, and better maintain mechanical strength when exposed to a high temperature and high humidity environment in combination with a thermosetting resin and an inorganic filler. The conditions for this mass ratio may be, for example, 3 or less, 2.5 or less, 2 or less, etc.
[0128] Resin X has a glass transition temperature of 25°C or less. If resin X has only one glass transition temperature, its glass transition temperature is 25°C or less. If resin X has multiple glass transition temperatures, at least one glass transition temperature is 25°C or less. In the case where resin X has multiple glass transition temperatures, there is no particular limitation on the other glass transition temperatures as long as the glass transition temperature is 25°C or less. In combination with a thermosetting resin and an inorganic filler, from the viewpoint of producing a cured product that exhibits better folding resistance and insulation reliability and better heat resistance characteristics (substrate adhesion after reflow soldering), the glass transition temperature of resin X below 25°C is preferably 10°C or less, more preferably 5°C or less, and even more preferably 0°C or less.
[0129] In the present invention, the glass transition temperature of the resin X is based on a value measured by DSC (differential scanning calorimetry) at a temperature increase rate of 5° C. / min.
[0130] The weight average molecular weight Mw of the resin X is preferably 5,000 or more, more preferably 10,000 or more, further preferably 20,000 or more, 40,000 or more, 60,000 or more, 80,000 or more, or 100,000 or more, from the viewpoint of being able to enjoy the effects of the present invention. The upper limit of the Mw is not particularly limited, but is usually less than 1,000,000, preferably less than 800,000, more preferably less than 600,000, and further preferably less than 500,000.
[0131] In the present invention, the weight average molecular weight Mw of the resin X is based on a polystyrene-equivalent value measured by gel permeation chromatography (GPC).
[0132] -Synthesis of Resin X-
[0133] The synthesis process of the resin X is not particularly limited as long as the resin X can achieve a structure including the above-mentioned oligophenylene ether skeleton and the flexible skeleton.
[0134] An example of the synthesis procedure of the resin X is shown below.
[0135] In one embodiment, the resin X is obtained by reacting the following compounds:
[0136] (x1) polyol compounds containing a flexible skeleton;
[0137] (x2) polyisocyanate compounds;
[0138] (x3) anhydride group-containing compounds; and
[0139] (x4) A polyol compound containing an oligophenylene ether skeleton.
[0140] In the reaction involved, the flexible skeleton of component (x1) is bonded to the oligophenylene ether skeleton of component (x4) via the imide structure (preferably a cyclic imide structure) generated by the reaction of component (x2) and component (x3). Therefore, in one embodiment, resin X contains an imide structure (preferably a cyclic imide structure).
[0141] Regarding the component (x1), suitable examples of the flexible skeleton are as described above. As the component (x1), any polyol compound containing a flexible skeleton can be used according to the structure of the target resin X (i.e., the flexible skeleton), and examples of commercial products thereof are as described above in connection with the flexible skeleton. The component (x1) can be used alone or in combination of two or more, depending on the type of the flexible skeleton contained in the resin X.
[0142] The type of the polyisocyanate compound as component (x2) is not particularly limited as long as it can react with a hydroxyl group and react with component (x3) to form an imide structure. Examples of the polyisocyanate compound include aliphatic diisocyanate compounds such as butane diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate; alicyclic diisocyanate compounds such as norbornane diisocyanate, isophorone diisocyanate, cyclohexane dimethyl diisocyanate, and 4,4'-methylenebiscyclohexyl diisocyanate; phenylene diisocyanate (p-phenylene diisocyanate, m-phenylene diisocyanate), phenylenediisocyanate (p-phenylenediisocyanate, m-phenylenediisocyanate), and phenylenediisocyanate (p-phenylenediisocyanate, m-phenylenediisocyanate). ester), toluene diisocyanate (toluene-2,4-diisocyanate, toluene-2,6-diisocyanate), diphenylmethane-4,4'-diisocyanate, dimethylbiphenyl diisocyanate, diethylbiphenyl diisocyanate, meta-phenylenediisocyanate, 1,3-bis(α,α-dimethylisocyanatemethyl)benzene, tetramethylphenylenediisocyanate, 4,4'-oxybis(isocyanatebenzene), naphthalene diisocyanate aromatic diisocyanate compounds; polymethylene polyphenyl polyisocyanate; their isocyanurate modified bodies, biuret modified bodies, allophanate modified bodies, etc. Component (x2) may be used alone or in combination of two or more.
[0143] As the compound containing anhydride groups as component (x3), there is no particular limitation on the type thereof as long as it can react with component (x2) to form an imide structure (preferably a cyclic imide structure). As the compound containing anhydride groups, tetracarboxylic dianhydride is preferably used, and examples thereof include: pyromellitic dianhydride, benzophenone tetracarboxylic dianhydride, biphenyl tetracarboxylic dianhydride, naphthalene tetracarboxylic dianhydride, oxydiphthalic anhydride, p-phenylene bis(trimellitic anhydride ester), 4,4'-(hexafluoroisopropylidene) diphthalic anhydride, cyclobutane tetracarboxylic anhydride, cyclopentane tetracarboxylic anhydride, 3,3'-4,4'-diphenyl sulfone tetracarboxylic dianhydride, and 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione. The component (x3) may be used alone or in combination of two or more.
[0144] Regarding the component (x4), suitable examples of oligophenylene ether skeletons are as described above. As the component (x4), any polyol compound containing an oligophenylene ether skeleton can be used according to the structure of the target resin X (i.e., the oligophenylene ether skeleton). For example, as a polyol compound containing an oligophenylene ether skeleton represented by the above formula (2-1), "NORYL SA90" manufactured by Sabic can be cited. The component (x4) can be used alone or in combination of two or more, depending on the type of oligophenylene ether skeleton contained in the resin X.
[0145] Regarding the synthesis reaction of resin X using these (x1) to (x4) components, it is sufficient to carry out the reaction under the conditions generally used in the imidization reaction using a polyol compound, an isocyanate compound and an anhydride group-containing compound. The reaction raw materials containing the (x1) to (x4) components may be reacted together, or the (x1) to (x4) components may be reacted in sequence. In the case where the reaction raw materials containing the (x1) to (x4) components are reacted together, the reaction temperature may be set to, for example, a range of 100 to 160° C., and the reaction time may be set to, for example, a range of 4 to 10 hours. In addition, in the case where the (x1) to (x4) components are reacted in sequence, after the (x1) component and the (x2) component are reacted at, for example, a range of 50 to 100° C. for 0.5 to 4 hours, the (x3) component and the (x4) component may be added, for example, and reacted at, for example, a range of 120 to 160° C. for 3 to 6 hours.
[0146] In the reaction of components (x1) to (x4), a catalyst may be used. Examples of the catalyst include tertiary amines such as tetramethylbutylene diamine, benzyl dimethylamine, triethanolamine, triethylamine, N,N'-dimethylpiperidine, α-methylbenzyl dimethylamine, N-methylmorpholine, and triethylenediamine; and organic metal catalysts such as dibutyltin laurate, dimethyltin dichloride, cobalt naphthenate, and zinc naphthenate.
[0147] In the reaction involved, by changing the degree of reaction between the component (x1) and the component (x2), or the quantitative ratio between the component (x1) and the component (x4), the molecular weight of the resin X or the proportion of the flexible skeleton in the resin X can be adjusted, and thus the glass transition temperature of the resin X can be adjusted.
[0148] From the viewpoint of bringing a cured product that exhibits good folding resistance and insulation reliability and good heat resistance (substrate adhesion after reflow soldering), the mass ratio of resin X to inorganic filler (resin X / inorganic filler) is preferably 0.3 or more, more preferably 0.5 or more, and further preferably 0.6 or more, 0.8 or more, 1 or more, more than 1, 1.1 or more, or 1.2 or more. In particular, if the mass ratio of resin X / inorganic filler exceeds 1, it is easy to obtain a cured product that is excellent in all aspects of folding resistance, insulation reliability, and heat resistance, and therefore is suitable. With regard to the upper limit of the mass ratio, from the same viewpoint, it is preferably 3 or less, more preferably 2.5 or less, and further preferably 2 or less, 1.8 or less, 1.6 or less, or 1.5 or less.
[0149] Regarding the content of the resin X in the resin composition, from the viewpoint of being able to enjoy the effect of the present invention more, when the resin component in the resin composition is set to 100% by mass, it is preferably 20% by mass or more, more preferably 25% by mass or more, further preferably 30% by mass or more, further preferably 35% by mass or more, 40% by mass or more, or 45% by mass or more, particularly preferably 50% by mass or more, 55% by mass or more, or 60% by mass or more, and its upper limit is preferably less than 85% by mass, 84% by mass or less, or 82% by mass or less, more preferably 80% by mass or less or less than 80% by mass. Therefore, in one embodiment, when the resin component in the resin composition is set to 100% by mass, the content of the resin X is 20% by mass or more and less than 85% by mass.
[0150] <Curing agent>
[0151] The resin composition of the present invention may further contain a curing agent.
[0152] The curing agent is not particularly limited, and examples thereof include active ester curing agents, phenol curing agents, naphthol curing agents, carbodiimide curing agents, acid anhydride curing agents, amine curing agents, benzoic acid curing agents, The curing agent may be a single curing agent or a combination of two or more curing agents. From the viewpoint of being able to enjoy the effect of the present invention more, the curing agent is preferably selected from one or more of an active ester curing agent, a phenol curing agent and a carbodiimide curing agent.
[0153] As active ester curing agent, a compound having more than one active ester group in one molecule can be used. Among them, as active ester curing agent, preferably phenolic esters, thiophenolic esters, N-hydroxylamine esters, esters of heterocyclic hydroxy compounds, etc. have more than two ester groups with high reactive activity in one molecule. The active ester curing agent is preferably obtained by the condensation reaction of carboxylic acid compounds and / or thiocarboxylic acid compounds with hydroxy compounds and / or thiol compounds. In particular, from the viewpoint of improving heat resistance, preferably active ester curing agents from carboxylic acid compounds, more preferably active ester curing agents obtained from carboxylic acid compounds and hydroxy compounds, and further preferably active ester curing agents obtained from carboxylic acid compounds and aromatic hydroxy compounds.
[0154] As the carboxylic acid compound, any of an aromatic carboxylic acid compound and an aliphatic carboxylic acid compound can be used, and examples thereof include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, pyromellitic acid, and halides thereof.
[0155] Examples of aromatic hydroxy compounds include: (i) addition polymerization products of unsaturated aliphatic cyclic compounds having two double bonds in one molecule and phenols; (ii) various bisphenol compounds; (iii) aromatic polyols having two or more hydroxyl groups bonded to carbon atoms on an aromatic ring; and (iv) aromatic monohydric alcohols having one hydroxyl group bonded to a carbon atom on an aromatic ring. Examples of addition polymerization products of unsaturated aliphatic cyclic compounds and phenols include: addition polymerization products of unsaturated aliphatic cyclic compounds such as dicyclopentadiene, tetrahydroindene, norbornadiene, limonene, and vinylcyclohexene and phenols which may have a substituent (e.g., phenol, cresol, xylenol, ethylphenol, propylphenol, vinylphenol, allylphenol, phenylphenol, benzylphenol, halogenated phenol, etc.). Specifically, examples include: dicyclopentadiene-phenol addition polymers. Examples of the bisphenol compound include bisphenol A, bisphenol F, bisphenol AF, bisphenol AP, bisphenol B, bisphenol BP, bisphenol C, and bisphenol M. Examples of the aromatic polyol having two or more hydroxyl groups bonded to carbon atoms on an aromatic ring include hydroquinone, resorcinol, catechol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, benzenetriol, and phenol novolac. Examples of the aromatic monohydric alcohol having one hydroxyl group bonded to a carbon atom on an aromatic ring include phenol, cresol, xylenol, ethylphenol, propylphenol, vinylphenol, allylphenol, phenylphenol, benzylphenol, halogenated phenol, naphthol, methylnaphthol, dimethylnaphthol, ethylnaphthol, propylnaphthol, vinylnaphthol, allylnaphthol, phenylnaphthol, benzylnaphthol, halogenated naphthols, and the like.
[0156] Suitable specific examples of active ester curing agents include active ester compounds containing dicyclopentadiene diphenol structures, active ester compounds containing naphthalene structures, active ester compounds containing acetylated products of phenol novolacs, and active ester compounds containing benzoylated products of phenol novolacs. Among them, active ester compounds containing naphthalene structures and active ester compounds containing dicyclopentadiene diphenol structures are more preferred. "Dicyclopentadiene diphenol structure" means a divalent structural unit composed of phenylene-dicyclopentenylene-phenylene.
[0157] Commercially available active ester curing agents include "EXB9451", "EXB9460", "EXB9460S", "HPC-8000L-65TM", "HPC-8000-65T", "HPC-8000H", and "HPC-8000H-65TM" (manufactured by DIC Corporation) as active ester compounds containing a dicyclopentadiene-type diphenol structure; "HP-B-8151-62T", "EXB-8100L-65T", "EXB-9416-70BK", and "HPC-8 150-62T", "EXB-8" (manufactured by DIC Corporation); as the phosphorus-containing active ester compound, "EXB9401" (manufactured by DIC Corporation) can be cited; as the active ester compound as the acetylated product of phenol novolac, "DC808" (manufactured by Mitsubishi Chemical Corporation) can be cited; as the active ester compound as the benzoylated product of phenol novolac, "YLH1026", "YLH1030" and "YLH1048" (manufactured by Mitsubishi Chemical Corporation) can be cited; as the active ester compound containing a styryl group and a naphthalene structure, "PC1300-02-65MA" (manufactured by AIR WATER Corporation) and the like can be cited.
[0158] As phenolic curing agent and naphthol curing agent, from the viewpoint of heat resistance and water resistance, preferably the phenolic curing agent with novolac structure or the naphthol curing agent with novolac structure. In addition, from the viewpoint of the insulating layer that can reach the good adhesion strength (peel strength) with the conductor layer, preferably nitrogen-containing phenolic curing agent or nitrogen-containing naphthol curing agent, more preferably the phenolic curing agent containing triazine skeleton or the naphthol curing agent containing triazine skeleton. Wherein, from the viewpoint of highly satisfying heat resistance, water resistance and the adhesion strength with the conductor layer, preferably the phenolic novolac resin containing triazine skeleton or the naphthol novolac resin containing triazine skeleton.
[0159] Specific examples of phenol-based curing agents and naphthol-based curing agents include: "MEH-7700", "MEH-7810", "MEH-7851", and "MEH-8000H" manufactured by Meiwa Chemicals; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-495V", and "SN-375" manufactured by Nippon Steel Chemicals Co., Ltd. , "SN-395"; "TD-2090", "TD-2090-60M", "LA-7052", "LA-7054", "LA-1356", "LA-3018", "LA-3018-50P", "EXB-9500", "HPC-9500", "KA-1160", "KA-1163", "KA-1165" manufactured by DIC; "GDP-6115L", "GDP-6115H", "ELPC75" and other products manufactured by Qunrong Chemical Co., Ltd.
[0160] Examples of the carbodiimide curing agent include curing agents having one or more, preferably two or more carbodiimide structures in one molecule, for example, aliphatic biscarbodiimides such as tetramethylene-bis(tert-butylcarbodiimide) and cyclohexanebis(methylene-tert-butylcarbodiimide); biscarbodiimides such as aromatic biscarbodiimides such as phenylene-bis(xylylcarbodiimide); aliphatic polycarbodiimides such as polyhexamethylenecarbodiimide, polytrimethylhexamethylenecarbodiimide, polycyclohexylenecarbodiimide, poly(methylenebiscyclohexylenecarbodiimide), poly(isophoronecarbodiimide); Imides; poly(phenylene carbodiimide), poly(naphthylene carbodiimide), poly(toluene carbodiimide), poly(methyl diisopropyl phenylene carbodiimide), poly(triethyl phenylene carbodiimide), poly(diethyl phenylene carbodiimide), poly(triisopropyl phenylene carbodiimide), poly(diisopropyl phenylene carbodiimide), poly(xylylene carbodiimide), poly(tetramethyl xylylene carbodiimide), poly(methylene diphenylene carbodiimide), poly[methylene bis(methyl phenylene) carbodiimide] and the like aromatic polycarbodiimides.
[0161] Examples of commercially available carbodiimide curing agents include "CARBODILITE V-02B", "CARBODILITE V-03", "CARBODILITE V-04K", "CARBODILITE V-07" and "CARBODILITE V-09" manufactured by Nisshinbo Chemical Co., Ltd.; and "Stabaxol P", "Stabaxol P400" and "Hycasyl 510" manufactured by LANXESS.
[0162] Examples of the acid anhydride curing agent include a curing agent having one or more acid anhydride groups in one molecule, preferably a curing agent having two or more acid anhydride groups in one molecule. Specific examples of the acid anhydride curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenylsuccinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, dicarboxylic anhydride, and the like. Polymer-type acid anhydrides such as benzophenone tetracarboxylic dianhydride, biphenyl tetracarboxylic dianhydride, naphthalene tetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfone tetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-c]furan-1,3-dione, ethylene glycol bis(trimellitic anhydride), styrene-maleic acid resin obtained by copolymerization of styrene and maleic acid, etc. Commercially available products of anhydride curing agents include: "HNA-100", "MH-700", "MTA-15", "DDSA", and "OSA" manufactured by Shin Nippon Chemical Co., Ltd.; "YH-306" and "YH-307" manufactured by Mitsubishi Chemical Corporation; "HN-2200" and "HN-5500" manufactured by Resonac; and "EF-30", "EF-40", "EF-60", and "EF-80" manufactured by Cray Valley Corporation.
[0163] As the amine curing agent, there can be mentioned: a curing agent having one or more, preferably two or more amino groups in one molecule, for example: aliphatic amines, polyether amines, alicyclic amines, aromatic amines, etc. Among them, aromatic amines are preferred from the viewpoint of exerting the desired effect of the present invention. The amine curing agent is preferably a primary amine or a secondary amine, and more preferably a primary amine. Specific examples of the amine curing agent include: 4,4'-methylenebis(2,6-dimethylaniline), 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, metaphenylenediamine, metaphenylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, 2,2-bis(3-amino-4-hydroxy phenyl)propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, etc. As the amine curing agent, commercially available products can be used, for example, "SEIKACURE-S" manufactured by SEIKA Corporation; "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", and "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd.; and "EPICURE W" manufactured by Mitsubishi Chemical Corporation.
[0164] As benzo Specific examples of the oxazine-based curing agent include "JBZ-OP100D" and "ODA-BOZ" manufactured by JFE Chemical Co., Ltd.; "HFB2006M" manufactured by Showa High Molecular Co., Ltd.; and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.
[0165] Examples of the cyanate curing agent include difunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate (oligo(3-methylene-1,5-phenylene cyanate)), 4,4′-methylenebis(2,6-dimethylphenylcyanate), 4,4′-ethylenediphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanatephenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanatephenyl-1-(methylethylene))benzene, bis(4-cyanatephenyl)sulfide and bis(4-cyanatephenyl)ether, polyfunctional cyanate resins derived from phenol novolac and cresol novolac, and prepolymers obtained by partially triazinizing these cyanate resins. Specific examples of cyanate curing agents include "PT30" and "PT60" manufactured by Arxada (both are phenol novolac-type multifunctional cyanate resins), "BA230", "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate is triazine-treated to become trimers), etc.
[0166] Examples of the thiol-based curing agent include trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), and tris(3-mercaptopropyl)isocyanurate.
[0167] The reactive group equivalent of the curing agent is preferably 50 g / eq. to 3000 g / eq., more preferably 100 g / eq. to 1000 g / eq., further preferably 100 g / eq. to 500 g / eq., and particularly preferably 100 g / eq. to 300 g / eq. The reactive group equivalent is the mass of the curing agent per 1 equivalent of reactive groups.
[0168] From the viewpoint of easily achieving a cured product with a low dielectric loss tangent, the curing agent preferably includes an active ester curing agent. When the curing agent includes an active ester curing agent, when the non-volatile component in the curing agent is set to 100% by mass, the content of the active ester curing agent is preferably 30% by mass or more, more preferably 40% by mass or more, further preferably 45% by mass or more or 50% by mass or more, and the upper limit thereof may be 100% by mass, for example, 98% by mass or less, 95% by mass or less, or 90% by mass or less.
[0169] When the resin combination of the present invention includes a curing agent, the content of the curing agent in the resin combination is not particularly limited, when the resin component in the resin combination is set to 100 mass %, preferably more than 1 mass %, more preferably more than 3 mass %, further preferably more than 5 mass %, more than 6 mass % or more than 7 mass %. The upper limit of the content of the curing agent is preferably less than 50 mass %, more preferably less than 40 mass %, less than 35 mass %, less than 30 mass % or less than 25 mass %.
[0170] <Curing accelerator>
[0171] The resin composition of the present invention may further include a curing accelerator. By including a curing accelerator, the curing time and the curing temperature can be effectively adjusted.
[0172] Examples of the curing accelerator include phosphorus curing accelerators, urea curing accelerators, guanidine curing accelerators, imidazole curing accelerators, metal curing accelerators, and amine curing accelerators. From the perspective of being able to enjoy the effects of the present invention, the curing accelerator preferably includes an amine curing accelerator or an imidazole curing accelerator, and more preferably includes an imidazole curing accelerator. One curing accelerator may be used alone, or two or more may be used in combination.
[0173] Examples of phosphorus-based curing accelerators include tetrabutylphosphonium bromide, tetrabutylphosphonium chloride, tetrabutylphosphonium acetate, tetrabutylphosphonium decanoate, tetrabutylphosphonium laurate, bis(tetrabutylphosphonium)pyromellitic acid salt, tetrabutylphosphonium hexahydrophthalate, and tetrabutylphosphonium bis(tetrabutylphosphonium) pyromellitic acid salt. aliphatic phosphonium salts such as phosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate and di-tert-butylmethylphosphonium tetraphenylborate; methyltriphenylphosphonium bromide, ethyltriphenylphosphonium bromide, propyltriphenylphosphonium bromide, Aromatic phosphonium salts such as butyltriphenylphosphonium, benzyltriphenylphosphonium chloride, tetraphenylphosphonium bromide, p-tolyltriphenylphosphonium tetra-p-tolylborate, tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, butyltriphenylphosphonium thiocyanate; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone addition products such as triphenylphosphine-p-benzoquinone addition products reactants; aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine; dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tri(4-ethylphenyl)phosphine, tri(4-propylphenyl)phosphine, tri(4-isopropylphenyl)phosphine, tri(4-butylphenyl)phosphine, tri(4-tert-butylphenyl)phosphine, tri(2,4-dimethylphenyl)phosphine, tri(2,5-dimethylphenyl)phosphine phenyl)phosphine, tri(2,6-dimethylphenyl)phosphine, tri(3,5-dimethylphenyl)phosphine, tri(2,4,6-trimethylphenyl)phosphine, tri(2,6-dimethyl-4-ethoxyphenyl)phosphine, tri(2-methoxyphenyl)phosphine, tri(4-methoxyphenyl)phosphine, tri(4-ethoxyphenyl)phosphine, tri(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, 2,2'-bis(diphenylphosphino)diphenyl ether and the like.
[0174] Examples of the urea curing accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, 3-(3,4-dimethylphenyl)-1, Aromatic dimethyl urea such as 1-dimethyl urea, 3-(4-isopropylphenyl)-1,1-dimethyl urea, 3-(4-methoxyphenyl)-1,1-dimethyl urea, 3-(4-nitrophenyl)-1,1-dimethyl urea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethyl urea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethyl urea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethyl urea, N,N-(1,4-phenylene)bis(N',N'-dimethyl urea), N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethyl urea)[toluene bis(dimethyl urea)].
[0175] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanidine, 1-ethylbiguanidine, 1-n-butylbiguanidine, 1-n-octadecylbiguanidine, 1,1-dimethylbiguanidine, 1,1-diethylbiguanidine, 1-cyclohexylbiguanidine, 1-allylbiguanidine, 1-phenylbiguanidine, and 1-(o-tolyl)biguanidine.
[0176] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, 1-cyanoethyl-2-phenylimidazole trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1' imidazole compounds such as 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, and adducts of imidazole compounds with epoxy resins.
[0177] As the imidazole curing accelerator, commercially available products can be used, for example, "1B2PZ", "2E4MZ", "2MZA-PW", "2MZ-OK", "2MA-OK", "2MA-OK-PW", "2P4MZ", "2PHZ", "2PHZ-PW", "Cl1Z", "Cl1Z-CN", "Cl1Z-CNS", "C11Z-A" manufactured by Shikoku Chemical Industry Co., Ltd.; "P200-H50" manufactured by Mitsubishi Chemical Corporation, etc. These may be used alone or in combination of two or more.
[0178] As metal curing accelerators, for example, organic metal complexes or organic metal salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin can be cited. Specific examples of organic metal complexes include organic cobalt complexes such as cobalt acetylacetonate (II) and cobalt acetylacetonate (III), organic copper complexes such as copper acetylacetonate (II), organic zinc complexes such as zinc acetylacetonate (II), organic iron complexes such as iron acetylacetonate (III), organic nickel complexes such as nickel acetylacetonate (II), and organic manganese complexes such as manganese acetylacetonate (II). As organic metal salts, for example, zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, zinc stearate, and the like can be cited.
[0179] Examples of the amine-based curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine (DMAP), benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene. A commercially available amine-based curing accelerator may be used, and examples thereof include "MY-25" manufactured by Ajinomoto Fine-Techno Co., Ltd.
[0180] When the resin composition of the present invention contains a curing accelerator, the content of the curing accelerator in the resin composition is not particularly limited. When the resin component in the resin composition is set to 100% by mass, it is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, and further preferably 0.05% by mass or more. The upper limit is preferably 3% by mass or less, more preferably 2% by mass or less, 1.5% by mass or less, or 1% by mass or less.
[0181] <Compounds having a radically polymerizable unsaturated group>
[0182] The resin composition of the present invention may contain a compound having a free radical polymerizable unsaturated group as an optional component. By containing a compound having a free radical polymerizable unsaturated group, it is easy to achieve a resin composition that can produce a cured product that exhibits better folding resistance and insulation reliability and better heat resistance (substrate adhesion after reflow soldering), and therefore it is suitable.
[0183] The compound having a radical polymerizable unsaturated group may be used alone or in combination of two or more.
[0184] As a compound having a free radical polymerizable unsaturated group, as long as there are more than one (preferably more than two) free radical polymerizable unsaturated groups in one molecule, its type is not particularly limited. As a compound containing a free radical polymerizable unsaturated group, for example, there can be mentioned: a compound having one or more selected from maleimide, vinyl, allyl, styryl, vinylphenyl, acryloyl, methacryloyl, fumaryl and maleyl as a free radical polymerizable unsaturated group. Among them, from the viewpoint of easily realizing a resin composition that presents further good folding resistance and insulation reliability, and further good heat resistance (substrate adhesion after reflow soldering), it is preferably included in one or more selected from maleimide compounds, allyl compounds, styryl compounds and (meth) acrylic acid compounds.
[0185] The type of maleimide compound is not particularly limited as long as it has one or more (preferably two or more) maleimide groups (2,5-dihydro-2,5-dioxo-1H-pyrrol-1-yl) in one molecule. Examples of maleimide compounds include: (1) "BMI-3000J", "BMI-5000", "BMI-1400", "BMI-1500", "BMI-1700", and "BMI-689" (all Designer Molecules Inc.), "SLK-6895", "SLK-1500" (manufactured by Shin-Etsu Chemical Co., Ltd.), etc., containing an aliphatic skeleton (a divalent aliphatic group with more than 10 carbon atoms, particularly preferably an aliphatic skeleton with 36 carbon atoms derived from a dimer acid or a dimer diamine); (2) a maleimide compound containing an indane skeleton described in the Japan Invention Association's Public Technical Bulletin No. 2020-500211; (3) a maleimide compound containing an aromatic ring skeleton directly bonded to the nitrogen atom of the maleimide group, such as "MIR-3000-70MT" (manufactured by Nippon Kayaku Co., Ltd.), "BMI-4000" (manufactured by Yamato Chemical Co., Ltd.), and "BMI-80" (manufactured by KI Chemical Co., Ltd.).
[0186] As an allyl compound, as long as it has one or more (preferably two or more) allyl groups in one molecule, its type is not particularly limited, and it may be a monomer or an oligomer. As an allyl compound, for example, aromatic carboxylic acid allyl ester compounds such as diallyl biphenyl dicarboxylate, triallyl trimellitate, diallyl phthalate, diallyl isophthalate, diallyl terephthalate, diallyl 2,6-naphthalene dicarboxylate, and diallyl 2,3-naphthalene dicarboxylate can be cited; isocyanurate allyl ester compounds such as 1,3,5-triallyl isocyanurate and 1,3-diallyl-5-glycidyl isocyanurate; aromatic allyl compounds containing epoxy groups such as 2,2-bis[3-allyl-4-(glycidyloxy)phenyl]propane; bis[3-allyl-4-(3,4-dihydro-2H-1,3-benzo[3-allyl-4-(3,4-dihydro-2H-1,3-benzo[3-allyl-4-(3,4-dihydro-2H-1,3-benzo[3-allyl-4-(3,4-dihydro-2H-1,3-benzo[3-allyl-4-(3,4-dihydro-2H-1,3-benzo[3-allyl-4-(3,4-dihydro-2H-1,3-benzo[3-allyl-4-(3,4-dihydro-2H-1,3-benzo[3-allyl-4-(3,4-dihydro-2H-1,3-benzo[3-allyl- oxazine-3-yl)phenyl]methane and other benzoic acid-containing aromatic allyl compounds containing oxazine; ether-containing aromatic allyl compounds such as 1,3,5-triallyl ether benzene; allyl silane compounds such as diallyldiphenylsilane; resins each containing a plurality of benzene rings and allyl groups, etc.
[0187] Examples of commercially available allyl compounds include "MEH-8000H" and "MEH-8005" (allyl resins having a phenol ring) manufactured by Meiwa Chemicals Co., Ltd.; "ALP-d" (allyl resins having a benzophenone ring) manufactured by Shikoku Chemicals Co., Ltd.; "L-DAIC" manufactured by Shikoku Chemical Industry Co., Ltd. (allyl resin with an isocyanurate ring); "TAIC" manufactured by Nippon Chemical Co., Ltd. (allyl resin with an isocyanurate ring (triallyl isocyanurate)); "MDAC" manufactured by Osaka SODA Co., Ltd. (allyl resin with a cyclohexanedicarboxylic acid derivative); "DAD" manufactured by Nichikyu Techno Fine Chemical Co., Ltd. (diallyl biphenyldicarboxylate); "DAISO DAP Monomer" manufactured by Osaka SODA Co., Ltd. (diallyl phthalate), etc.
[0188] As the styryl compound, there is no particular limitation on its type as long as it has one or more (preferably two or more) styryl groups or vinylphenyl groups in one molecule, and it may be a monomer or an oligomer. Examples of the styryl compound include low molecular weight (molecular weight less than 1000) styryl compounds such as divinylbenzene, 2,4-divinyltoluene, 2,6-divinylnaphthalene, 1,4-divinylnaphthalene, 4,4'-divinylbiphenyl, 1,2-bis(4-vinylphenyl)ethane, 2,2-bis(4-vinylphenyl)propane, and bis(4-vinylphenyl)ether; and high molecular weight (molecular weight greater than 1000) styryl compounds such as vinylbenzyl-modified polyphenylene ether resins and styrene-divinylbenzene copolymers.
[0189] Examples of commercially available styrene-based compounds include "ODV-XET (X03)", "ODV-XET (X04)", and "ODV-XET (X05)" (styrene-divinylbenzene copolymers) manufactured by Nippon Steel Chemicals Co., Ltd.; and "OPE-2St1200" and "OPE-2St 2200" (vinyl benzyl-modified polyphenylene ether resins) manufactured by Mitsubishi Gas Chemicals Co., Ltd.
[0190] The (meth)acrylic compound is not particularly limited in type as long as it has one or more (preferably two or more) (meth)acryloyl groups in one molecule, and may be a monomer or an oligomer (excluding compounds corresponding to the component (C)). Examples of the (meth)acrylic acid compound include aliphatic (meth)acrylate compounds of low molecular weight (molecular weight less than 1000) such as cyclohexane-1,4-dimethanol di(meth)acrylate, cyclohexane-1,3-dimethanol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, glycerol tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate; and dimethacrylate compounds such as dimethacrylate. low molecular weight (molecular weight small) esters such as oxadiol di(meth)acrylate, 3,6-dioxa-1,8-octanediol di(meth)acrylate, 3,6,9-trioxaundecane-1,11-diol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, ethoxylated bisphenol A di(meth)acrylate, propoxylated bisphenol A di(meth)acrylate, etc. isocyanurate group-containing (meth)acrylate compounds with a molecular weight of less than 1000, such as tris(3-hydroxypropyl)isocyanurate tri(meth)acrylate, tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate, and ethoxylated isocyanuric acid tri(meth)acrylate; and high molecular weight (molecular weight of 1000 or more) acrylate compounds such as (meth)acrylic acid-modified polyphenylene ether resin.
[0191] Examples of commercially available (meth)acrylic acid compounds include "A-DOG" (dimethacrylic acid) manufactured by Shin-Nakamura Chemical Industry Co., Ltd. "DCP-A" (tricyclodecane dimethanol diacrylate) and "DCP" (tricyclodecane dimethanol dimethacrylate) manufactured by Kyoeisha Chemical Co., Ltd.; "KAYARAD R-684" (tricyclodecane dimethanol diacrylate) and "KAYARAD R-604" (dicyclodecane dimethanol dimethacrylate) manufactured by Nippon Kayaku Co., Ltd. "SA9000", "SA9000-111" (methacrylic acid modified polyphenylene ether) manufactured by SABIC, etc.
[0192] The radical polymerizable unsaturated group equivalent of the compound having a radical polymerizable unsaturated group is preferably 250 g / eq. to 1200 g / eq., and more preferably 300 g / eq. to 1100 g / eq. The radical polymerizable unsaturated group equivalent represents the mass of the compound having a radical polymerizable unsaturated group per 1 equivalent of the radical polymerizable unsaturated group. When the radical polymerizable unsaturated group equivalent of the compound having a radical polymerizable unsaturated group is within the above range, the effect of the present invention can be significantly obtained.
[0193] The Mw of the compound having a radical polymerizable unsaturated group is preferably 1000 to 40000, and more preferably 1500 to 35000. The Mw of the compound having a radical polymerizable unsaturated group can be measured as a polystyrene-equivalent value by a GPC method.
[0194] In the case where the resin composition of the present invention contains a compound having a free radical polymerizable unsaturated group, from the viewpoint of being able to better enjoy the effects of the present invention, the content of the compound having a free radical polymerizable unsaturated group in the resin composition is preferably 0.5% by mass or more, more preferably 1% by mass or more, further preferably 1.5% by mass or more, 2% by mass or more, or 2.5% by mass or more, when the resin component in the resin composition is set to 100% by mass, and the upper limit is preferably 30% by mass or less, more preferably 25% by mass or less, further preferably 20% by mass or less, 15% by mass or less, 14% by mass or less, 12% by mass or less, or 10% by mass or less.
[0195] <Other additives>
[0196] The resin composition of the present invention may further contain optional additives as non-volatile components. Examples of such additives include: organic fillers such as rubber particles, polyamide microparticles, and silicone particles; thermoplastic resins such as polycarbonate resins, phenoxy resins, polyvinyl acetal resins, polyolefin resins, polysulfone resins, polyethersulfone resins, polyphenylene ether resins, polyetheretherketone resins, and polyester resins; free radical polymerization initiators such as peroxide-based free radical polymerization initiators and azo-based free radical polymerization initiators; organic metal compounds such as organic copper compounds, organic zinc compounds, and organic cobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone-based leveling agents and acrylic polymer-based leveling agents; thickeners such as Benton and montmorillonite. Agent; defoamers such as silicone defoamers, acrylic defoamers, fluorine defoamers, and vinyl resin defoamers; ultraviolet absorbers such as benzotriazole ultraviolet absorbers; adhesion enhancers such as urea silane; adhesion imparting agents such as triazole adhesion imparting agents, tetrazole adhesion imparting agents, and triazine adhesion imparting agents; antioxidants such as hindered phenol antioxidants and hindered amine antioxidants; fluorescent whitening agents such as stilbene derivatives; surfactants such as fluorine surfactants and silicone surfactants; flame retardants other than non-reactive phosphazene compounds such as phosphorus flame retardants (such as phosphate compounds, phosphazene compounds, phosphinic acid compounds, and red phosphorus), nitrogen flame retardants (such as melamine sulfate), halogen flame retardants, and inorganic flame retardants (such as antimony trioxide). One additive can be used alone, or two or more additives can be used in combination at any ratio. The content of other additives can be appropriately set by those skilled in the art.
[0197] <Organic solvents>
[0198] In addition to the non-volatile components described above, the resin composition of the present invention may further contain an optional organic solvent as a volatile component. As the organic solvent, a known organic solvent may be used appropriately, and the type thereof is not particularly limited. Examples of the organic solvent include: ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, and γ-butyrolactone; tetrahydropyran, tetrahydrofuran, 1,4-dihydropyran, and the like. Ether solvents such as alkane, diethyl ether, diisopropyl ether, dibutyl ether, diphenyl ether; alcohol solvents such as methanol, ethanol, propanol, butanol, ethylene glycol; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, carbitol acetate (ethyl diglycol Ether ester solvents such as acetate, γ-butyrolactone, and methyl methoxypropionate; ester alcohol solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate; ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butyl carbitol); amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; sulfoxide solvents such as dimethyl sulfoxide; nitrile solvents such as acetonitrile and propionitrile; aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane; aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. The organic solvent may be used alone or in combination of two or more in any ratio.
[0199] Resin combination of the present invention can for example be manufactured as follows: the components of the resin X containing the oligophenylene ether skeleton, the thermosetting resin, the inorganic filling material, the further curing agent as required, the curing accelerator, the compound with the free radical polymerizable unsaturated group, the other additives and the organic solvent are added in any reaction vessel and mixed in any order and / or in part or in whole at the same time, thus manufactured. In addition, in the process of adding each component to mix, the temperature can be suitably set, and heating and / or cooling can be performed temporarily or all the time. In addition, in the process of adding each component to mix, stirring or vibration can be performed. In addition, when adding and mixing or afterwards, for example, stirring devices such as mixers can be used to stir the resin combination so that it is evenly dispersed.
[0200] The resin composition of the present invention comprises a thermosetting resin, an inorganic filler, and a resin X having an oligophenylene ether skeleton and a glass transition temperature of 25° C. or less, wherein the cured product thereof exhibits a dielectric loss tangent Df of less than 0.01 and satisfies at least one of the following conditions (1) and (2):
[0201] (1) The elongation is 5% or more and less than 50%;
[0202] (2) The number of folding times in the MIT folding test is 200 times or more.
[0203] According to such a resin composition, a cured product having excellent folding resistance and insulation reliability and also excellent heat resistance characteristics (adhesion to the substrate after reflow) can be obtained.
[0204] From the viewpoint of producing a cured product that exhibits good folding resistance and insulation reliability and also has good heat resistance (substrate adhesion after reflow soldering), it is important that the cured product of the resin composition of the present invention exhibits a dielectric loss tangent Df of less than 0.01. For example, as described in the <Determination of dielectric loss tangent> column described later, when measured at 5.8 GHz and 23° C., the dielectric loss tangent Df of the cured product of the resin composition of the present invention is less than 0.01, preferably less than 0.009, less than 0.008, or less than 0.007.
[0205] From the viewpoint of providing a cured product that exhibits good folding resistance and insulation reliability and also has good heat resistance (substrate adhesion after reflow), it is important that the cured product of the resin composition of the present invention satisfies at least one of the following conditions (1) and (2):
[0206] (1) The elongation is 5% or more and less than 50%;
[0207] (2) The number of folding times in the MIT folding test is 200 times or more.
[0208] The above-mentioned condition (1) is described in detail. It is important that the cured product of the resin composition of the present invention has an elongation (elongation at breaking point) of 5% or more and less than 50%, as measured by the method described in the "Evaluation of Elongation" column described later. The lower limit is preferably 6% or more, more preferably 8% or more, and further preferably 10% or more. The upper limit is preferably 45% or less, more preferably 40% or less, and further preferably 35% or less or 30% or less.
[0209] The above condition (2) is described in detail. It is important that the cured product of the resin composition of the present invention has a folding resistance of 200 times or more, preferably 220 times or more, more preferably 240 times or more, and further preferably 250 times or more, 260 times or more, 280 times or more, or 300 times or more, as measured by the method described in the column "Evaluation of folding resistance in MIT test" described later. The upper limit of the folding resistance is not particularly limited, and may be, for example, 2000 times or less, 1500 times or less, 1000 times or less, etc.
[0210] The cured product of the resin composition of the present invention has the characteristic of exhibiting good insulation reliability. The cured product of the resin composition of the present invention preferably has an insulation resistance value of 1.00×10 8 Ω or more, more preferably 5.00×10 8 Ω or more, more preferably 1.00×10 9 Ω or more.
[0211] The cured product of the resin composition of the present invention has the characteristic of showing good heat resistance (conductor adhesion after reflow soldering). The cured product of the resin composition of the present invention has a peel strength after reflow soldering measured according to JIS C6481, for example, as described in the column of <Evaluation of substrate adhesion> described later, preferably 0.4kgf / cm or more, more preferably 0.45kgf / cm or more, further preferably 0.5kgf / cm or more, 0.55kgf / cm or more, 0.6kgf / cm or more, 0.65kgf / cm or more, or 0.7kgf / cm or more.
[0212] The resin composition of the present invention can bring a cured product showing good folding resistance and insulation reliability and good heat resistance (substrate adhesion after reflow soldering). Therefore, the resin composition of the present invention can be suitably used as a resin composition (resin composition for insulating layer of printed wiring board) for forming the insulating layer of printed wiring board, and can be more suitably used as a resin composition (resin composition for interlayer insulating layer of printed wiring board) for forming the interlayer insulating layer of printed wiring board. Among them, it can be suitably used as a resin composition (resin composition for insulating layer of flexible substrate) for forming the insulating layer of flexible printed wiring board (flexible substrate), and can be more suitably used as a resin composition (resin composition for interlayer insulating layer of flexible substrate) for forming the interlayer insulating layer of flexible substrate. The resin composition of the present invention can also be widely used in solder resist, bottom filling material, chip bonding material, semiconductor sealing material, hole filling resin, component embedding resin, etc.
[0213] [Sheet-like laminated materials (resin sheets, prepregs)]
[0214] The resin composition of the present invention may be used as it is, or may be used in the form of a sheet-like laminated material containing the resin composition.
[0215] As the sheet-like laminated material, the following resin sheets and prepregs are preferred.
[0216] In one embodiment, the resin sheet includes a support and a layer of a resin composition provided on the support (hereinafter simply referred to as a "resin composition layer"), wherein the resin composition layer is formed of the resin composition of the present invention.
[0217] The thickness of the resin composition layer is suitable for different values according to the purpose, and can be appropriately determined according to the purpose. For example, from the viewpoint of thinning the flexible printed wiring board, the thickness of the resin composition layer is preferably 100 μm or less, 80 μm or less, 60 μm or less, 50 μm or less, 40 μm or less, or 30 μm or less. The lower limit of the thickness of the resin composition layer is not particularly limited, and can usually be 1 μm or more, 5 μm or more, etc.
[0218] Examples of the support include thermoplastic resin films, metal foils, and release papers, and thermoplastic resin films and metal foils are preferred. Therefore, in a preferred embodiment, the support is a thermoplastic resin film or a metal foil.
[0219] When a thermoplastic resin film is used as a support, examples of the thermoplastic resin include polyesters such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), acrylics such as polycarbonate (PC) and polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among them, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0220] When a metal foil is used as a support, examples of the metal foil include copper foil and aluminum foil, preferably copper foil. The copper foil may be a foil made of copper alone or an alloy of copper and other metals (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.).
[0221] For the support, the surface bonded to the resin composition layer may also be subjected to matte treatment, corona treatment, and antistatic treatment. In addition, as the support, a support with a release layer having a release layer on the surface bonded to the resin composition layer may be used. As a release agent used in the release layer of the support with a release layer, for example, there can be mentioned: one or more release agents selected from alkyd resins, polyolefin resins, urethane resins, and silicone resins. The support with a release layer can use commercial products, for example, there can be mentioned: "SK-1", "AL-5", "AL-7" manufactured by Lintec Corporation, which is a PET film having a release layer with an alkyd resin-based release agent as the main component; "Lumirror T60" manufactured by Toray Industries, Inc.; "Purex" manufactured by Teijin Co., Ltd.; "Unipeel" manufactured by Unitika Corporation, etc.
[0222] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, the thickness of the entire support with a release layer is preferably in the above range.
[0223] When a metal foil is used as a support, a metal foil with a support substrate in which a peelable support substrate is attached to a thin metal foil can be used. In one embodiment, the metal foil with a support substrate comprises: a support substrate, a peeling layer provided on the support substrate, and a metal foil provided on the peeling layer. When a metal foil with a support substrate is used as a support, the resin composition layer is provided on the metal foil.
[0224] In the metal foil with a supporting substrate, the material of the supporting substrate is not particularly limited, and examples thereof include: copper foil, aluminum foil, stainless steel foil, titanium foil, copper alloy foil, etc. When copper foil is used as the supporting substrate, it may be electrolytic copper foil or rolled copper foil. In addition, the peeling layer is not particularly limited as long as the metal foil can be peeled off from the supporting substrate, and examples thereof include: an alloy layer of an element selected from Cr, Ni, Co, Fe, Mo, Ti, W, and P; an organic film, etc.
[0225] In the metal foil with a supporting substrate, as a material of the metal foil, for example, copper foil and copper alloy foil are preferable.
[0226] In the metal foil with a supporting substrate, the thickness of the supporting substrate is not particularly limited, but is preferably in the range of 10 μm to 150 μm, more preferably in the range of 10 μm to 100 μm. The thickness of the metal foil can be, for example, in the range of 0.1 μm to 10 μm.
[0227] In one embodiment, the resin sheet may further include an optional layer as required. As the optional layer, for example, a protective film is provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface on the opposite side of the support). The thickness of the protective film is not particularly limited, for example, 1 μm to 40 μm. By laminating the protective film, dust and the like can be prevented from adhering to the surface of the resin composition layer or causing damage to the surface of the resin composition layer.
[0228] The resin sheet can be produced, for example, by directly applying a liquid resin composition on a support using a die coater or the like, or by preparing a resin varnish obtained by dissolving the resin composition in an organic solvent and applying the varnish on a support, followed by drying to form a resin composition layer.
[0229] Examples of the organic solvent include the same organic solvents as those described as the components of the resin composition. The organic solvent may be used alone or in combination of two or more.
[0230] Drying can be carried out by known methods such as heating and blowing hot air. The drying conditions are not particularly limited, and the drying is carried out in a manner such that the content of the organic solvent in the resin composition layer is 10% by mass or less, preferably 5% by mass or less. Although it varies depending on the boiling point of the organic solvent in the resin composition or resin varnish, for example, in the case of using a resin composition or resin varnish containing 30% by mass to 60% by mass of an organic solvent, a resin composition layer can be formed by drying at 50° C. to 150° C. for 3 minutes to 10 minutes.
[0231] The resin sheet can be stored by winding it into a roll. When the resin sheet has a protective film, it can be used by peeling off the protective film.
[0232] In one embodiment, the prepreg is formed by impregnating a sheet-like fiber base material with the resin composition of the present invention.
[0233] The sheet-like fiber substrate used for the prepreg is not particularly limited, and a sheet-like fiber substrate commonly used as a prepreg substrate such as glass cloth, aramid nonwoven fabric, liquid crystal polymer nonwoven fabric, etc. can be used. From the viewpoint of thinning a printed wiring board or a semiconductor chip package, the thickness of the sheet-like fiber substrate is preferably 50 μm or less, more preferably 40 μm or less, further preferably 30 μm or less, and particularly preferably 20 μm or less. There is no particular lower limit on the thickness of the sheet-like fiber substrate. It is usually 10 μm or more.
[0234] The prepreg can be produced by a known method such as a hot melt method or a solvent method.
[0235] The thickness of the prepreg may be in the same range as that of the resin composition layer in the above-mentioned resin sheet.
[0236] The sheet-like laminated material of the present invention can be suitably used to form an insulating layer of a printed wiring board (insulating layer for a printed wiring board), and can be more suitably used to form an interlayer insulating layer of a printed wiring board (interlayer insulating layer for a printed wiring board). Among them, it can be suitably used to form an insulating layer of a flexible substrate (insulating layer for a flexible substrate), and can be more suitably used to form an interlayer insulating layer of a flexible substrate (interlayer insulating layer for a flexible substrate).
[0237] [Laminated Sheet]
[0238] The laminated sheet is a sheet produced by laminating and curing a plurality of resin composition layers.
[0239] The laminated sheet includes a plurality of insulating layers which are cured products of the resin composition layer. Usually, the number of resin composition layers laminated for manufacturing the laminated sheet is consistent with the number of insulating layers contained in the laminated sheet. The number of specific insulating layers per laminated sheet is usually 2 or more, preferably 3 or more, particularly preferably 5 or more, preferably 20 or less, more preferably 15 or less, particularly preferably 10 or less.
[0240] The laminated sheet is a sheet used by bending with one side facing the other. The minimum bending radius of the laminated sheet is not particularly limited, but is preferably 0.1 mm or more, more preferably 0.2 mm or more, further preferably 0.3 mm or more, preferably 5 mm or less, more preferably 4 mm or less, and particularly preferably 3 mm or less.
[0241] A hole may be formed in each insulating layer included in the laminated sheet, and the hole can function as a via hole or a through hole in the flexible substrate.
[0242] In addition to the insulating layer, the laminate may further include an optional element. For example, the laminate may include a conductor layer as an optional element. The conductor layer is usually partially formed on the surface of the insulating layer or between the insulating layers. The conductor layer usually functions as a wiring in the flexible substrate.
[0243] There is no particular limitation on the conductor material used for the conductor layer. In a suitable embodiment, the conductor layer includes one or more metals selected from gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor material may be a single metal or an alloy. As an alloy, for example, there can be mentioned: an alloy of two or more metals selected from the above (for example, nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy). Among them, from the viewpoint of versatility, cost, ease of patterning, etc. in forming the conductor layer, preferred are: chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper as a single metal; and alloys such as nickel-chromium alloy, copper-nickel alloy, and copper-titanium alloy. Among them, more preferred are: single metals of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper; and nickel-chromium alloy, and further preferred is: single metal of copper.
[0244] The conductor layer may be a single-layer structure or a multi-layer structure including two or more single metal layers or alloy layers composed of different types of metals or alloys. In the case where the conductor layer is a multi-layer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium or an alloy layer of nickel-chromium alloy.
[0245] The conductor layer may be patterned in order to function as wiring.
[0246] The thickness of the conductor layer is preferably 3 μm to 35 μm, more preferably 5 μm to 30 μm, further preferably 10 μm to 20 μm, and particularly preferably 15 μm to 20 μm, depending on the design of the flexible substrate.
[0247] The thickness of the laminated sheet is preferably 100 μm or more, more preferably 150 μm or more, and even more preferably 200 μm or more, and is preferably 2,000 μm or less, more preferably 1,000 μm or less, and even more preferably 500 μm or less.
[0248] <Method for producing laminated sheet>
[0249] The laminated sheet can be produced by a method including the steps of: (a) preparing a resin sheet; and (b) laminating and curing a plurality of resin composition layers using the resin sheet.
[0250] The order of lamination and curing of the resin composition layer is arbitrary as long as the desired laminated sheet is obtained. According to the components contained in the resin composition, for example, after all the multiple resin composition layers are laminated, the laminated multiple resin composition layers can be cured together. In addition, for example, whenever another resin composition layer is laminated on a certain resin composition layer, the laminated resin composition layer can also be cured.
[0251] A preferred embodiment of step (b) is described below. In the embodiments described below, for the purpose of distinction, the resin composition layers are appropriately numbered, such as "first resin composition layer" and "second resin composition layer", and further, the insulating layers obtained by curing these resin composition layers are also numbered in the same manner as the resin composition layers, such as "first insulating layer" and "second insulating layer".
[0252] In a preferred embodiment, step (b) comprises the following steps:
[0253] Step (II), curing the first resin composition layer to form a first insulating layer;
[0254] Step (VI), laminating a second resin composition layer on the first insulating layer; and
[0255] In step (VII), the second resin composition layer is cured to form a second insulating layer.
[0256] In addition, step (b) may include the following optional steps as needed:
[0257] Step (I), laminating a first resin composition layer on a sheet-like supporting substrate;
[0258] Step (III), opening a hole in the first insulating layer;
[0259] Step (IV), roughening the first insulating layer;
[0260] In step (V), a conductive layer is formed on the first insulating layer.
[0261] Hereinafter, each step will be described.
[0262] Step (I) is a step of laminating the first resin composition layer on the sheet-like supporting substrate before step (II). The sheet-like supporting substrate is a removable member, and for example, a plate-like, sheet-like, or film-like member is used.
[0263] The lamination of the sheet-like support substrate and the first resin composition layer can be implemented by vacuum lamination. In the vacuum lamination method, the heating and pressing temperature is preferably 60°C to 160°C, more preferably 80°C to 140°C, the heating and pressing pressure is preferably 0.098MPa to 1.77MPa, more preferably 0.29MPa to 1.47MPa, and the heating and pressing time is preferably 20 seconds to 400 seconds, more preferably 30 seconds to 300 seconds. Lamination is preferably implemented under reduced pressure conditions of 26.7hPa or less.
[0264] Lamination can be performed using a commercially available vacuum laminator. Examples of the commercially available vacuum laminator include a vacuum pressure laminator manufactured by Meiki Manufacturing Co., Ltd., a vacuum applicator manufactured by Nikko-Materials Co., Ltd., and a batch vacuum pressure laminator.
[0265] When a resin sheet is used, the lamination of the sheet-like support substrate and the first resin composition layer can be performed, for example, by pressing the resin sheet from the support body side and heating and pressing the first resin composition layer of the resin sheet onto the sheet-like support substrate. As a member for heating and pressing the resin sheet onto the sheet-like support substrate (hereinafter, sometimes appropriately referred to as a "heating and pressing member"), for example, a heated metal plate (SUS end plate, etc.) or a metal roller (SUS roller) can be cited. It is preferred that the heating and pressing member is not directly pressed onto the resin sheet, but is pressed through an elastic material such as a heat-resistant rubber so that the first resin composition layer fully follows the surface unevenness of the sheet-like support substrate.
[0266] After lamination, it is also possible to press, for example, with a heating and pressing component under normal pressure (under atmospheric pressure), thereby performing a smoothing treatment of the first resin composition layer. For example, when a resin sheet is used, the resin sheet is pressed with a heating and pressing component from the support side, thereby smoothing the first resin composition layer of the resin sheet. The pressing conditions for the smoothing treatment can be set to the same conditions as the heating and pressing conditions for the above-mentioned lamination. The smoothing treatment can be performed using a commercially available laminating machine. The lamination and smoothing treatment can also be performed continuously using the above-mentioned commercially available vacuum laminating machine.
[0267] Step (II) is a step of curing the first resin composition layer to form a first insulating layer. The curing conditions of the first resin composition layer are not particularly limited, and the conditions used when forming the insulating layer of the printed wiring board can be arbitrarily applied. The first resin composition layer can be cured by drying, but in the case of containing a thermosetting resin such as an epoxy resin, it can be cured by heat curing in addition to drying.
[0268] The specific heat curing conditions vary depending on the type of resin composition. For example, the curing temperature is preferably 120°C to 240°C, more preferably 150°C to 220°C, and further preferably 170°C to 210°C. In addition, the curing time is preferably 5 minutes to 120 minutes, more preferably 10 minutes to 110 minutes, and further preferably 20 minutes to 100 minutes.
[0269] Before the first resin composition layer is thermally cured, the first resin composition layer may be preheated at a temperature lower than the curing temperature. For example, before the first resin composition layer is thermally cured, the first resin composition layer may be preheated at a temperature of 50°C or more and less than 120°C (preferably 60°C or more and 115°C or less, more preferably 70°C or more and 110°C or less) for 5 minutes or more (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and further preferably 15 minutes to 100 minutes).
[0270] Step (III) is a step of opening a hole on the first insulating layer. Through this step (III), a via hole, a through hole, or the like can be formed on the first insulating layer. The opening can be performed using, for example, a drill, a laser, or a plasma, depending on the composition of the resin composition. The size and shape of the hole can be appropriately set according to the design of the flexible substrate.
[0271] Step (IV) is a step of roughening the first insulating layer. Usually, in step (IV), contamination is also removed. Therefore, the roughening treatment is sometimes called a decontamination treatment. Examples of the roughening treatment include a method of sequentially performing a swelling treatment based on a swelling solution, a roughening treatment based on an oxidant, and a neutralization treatment based on a neutralizing solution.
[0272] The swelling liquid is not particularly limited, and examples thereof include alkaline aqueous solutions such as sodium hydroxide aqueous solution and potassium hydroxide aqueous solution. Examples of commercially available swelling liquids include "Swelling DipSecuriganth P" and "Swelling DipSecuriganth SBU" manufactured by Atotech Japan. The swelling treatment based on the swelling liquid can be performed, for example, by immersing the cured body in a swelling liquid at 30°C to 90°C for 1 minute to 20 minutes. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferred to immerse the insulating layer in a swelling liquid at 40°C to 80°C for 5 minutes to 15 minutes.
[0273] The oxidant is not particularly limited, and examples thereof include alkaline permanganate solutions obtained by dissolving permanganate in an aqueous sodium hydroxide solution or an aqueous potassium hydroxide solution. The concentration of permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. As commercially available oxidants, examples thereof include alkaline permanganate solutions such as "Concentrate Compact P", "Concentrate Compact CP", and "Dosing Solution Securiganth P" manufactured by Atotech Japan. The roughening treatment based on the oxidant can be performed by immersing the cured body in an oxidant solution heated to 60°C to 80°C for 10 minutes to 30 minutes.
[0274] In addition, an acidic aqueous solution is used as a neutralizing solution. As a commercially available product, for example, "Reduction Solution Securiganth P" manufactured by Atotech Japan Co., Ltd. can be cited. The treatment based on the neutralizing solution can be carried out by immersing the solidified body in a neutralizing solution at 30°C to 80°C for 5 minutes to 30 minutes. In consideration of operability, etc., it is preferred to immerse the solidified body in a neutralizing solution at 40°C to 70°C for 5 minutes to 20 minutes.
[0275] The arithmetic mean roughness (Ra) of the surface of the roughened first insulating layer is preferably 400 nm or less, more preferably 300 nm or less, and further preferably 200 nm or less. The lower limit is not particularly limited, and may be 30 nm or more, 40 nm or more, or 50 nm or more.
[0276] Step (V) is a step of forming a conductor layer on the first insulating layer as needed. Examples of methods for forming the conductor layer include electroplating, sputtering, and evaporation, among which electroplating is preferred. As a suitable example, a method of electroplating the surface of the first insulating layer using an appropriate method such as a semi-additive method or a full-additive method to form a conductor layer having a desired wiring pattern can be cited. Among them, the semi-additive method is preferred from the viewpoint of manufacturing simplicity.
[0277] The following is an example of forming a conductor layer using a semi-additive method. First, a plating seed layer is formed on the surface of a first insulating layer by electroless plating. Then, a mask pattern is formed on the formed plating seed layer to expose a portion of the plating seed layer corresponding to a desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Thereafter, the unnecessary plating seed layer is removed by etching or the like, and a conductor layer having a desired wiring pattern can be formed.
[0278] In step (II), a first insulating layer is obtained, and after step (III), step (IV), and step (V) are performed as needed, step (VI) is performed. Step (VI) is a step of laminating a second resin composition layer on the first insulating layer. The lamination of the first insulating layer and the second resin composition layer can be performed by the same method as the lamination of the sheet-like supporting substrate and the first resin composition layer in step (I).
[0279] However, when the first resin composition layer is formed using a resin sheet, the support of the resin sheet is removed before step (VI). The support may be removed between step (I) and step (II), between step (II) and step (III), between step (III) and step (IV), or between step (IV) and step (V).
[0280] After step (VI), step (VII) is performed. Step (VII) is a step of curing the second resin composition layer to form a second insulating layer. The curing of the second resin composition layer can be performed by the same method as the curing of the first resin composition layer in step (II). Thus, a laminated sheet including a plurality of insulating layers such as the first insulating layer and the second insulating layer can be obtained.
[0281] In addition, in the method involved in the above-mentioned embodiment, the step (VIII) of opening a hole on the second insulating layer, the step (IX) of roughening the second insulating layer, and the step (X) of forming a conductor layer on the second insulating layer may be performed as needed. The opening of the second insulating layer in the step (VIII) may be performed by the same method as the opening of the first insulating layer in the step (III). In addition, the roughening treatment of the second insulating layer in the step (IX) may be performed by the same method as the roughening treatment of the first insulating layer in the step (IV). Moreover, the formation of the conductor layer on the second insulating layer in the step (X) may be performed by the same method as the formation of the conductor layer on the first insulating layer in the step (V).
[0282] In the above-mentioned embodiment, the embodiment of manufacturing a laminated sheet by stacking and curing two layers of resin composition layers, the first resin composition layer and the second resin composition layer, is described, but a laminated sheet can also be manufactured by stacking and curing more than three layers of resin composition layers. For example, in the method involved in the above-mentioned embodiment, the stacking and curing of the resin composition layer based on the process (VI) to the process (VII), and the opening of the insulating layer based on the process (VIII) to the process (X) as needed, the roughening treatment of the insulating layer and the formation of a conductor layer on the insulating layer can also be repeatedly implemented to manufacture the laminated sheet. Thus, a laminated sheet comprising more than three insulating layers is obtained.
[0283] Furthermore, the method according to the above-mentioned embodiment may include an optional step other than the above-mentioned step. For example, when the step (I) is performed, a step of removing the sheet-like supporting substrate may be performed.
[0284] [Flexible substrate]
[0285] The flexible substrate includes: a single-sided structure having a conductor layer only on one side of an insulating layer which is a cured product of a resin composition, a double-sided structure having a conductor layer on both sides of an insulating layer, and a multilayer structure (multilayer flexible substrate) in which insulating layers are laminated in a manner that conductors are three or more layers. The flexible substrate may include a laminate. In the case of including a laminate, the flexible substrate may include only the laminate, or may include an optional member in combination with the laminate. As optional members, for example, electronic components, cover films, etc. may be cited.
[0286] The flexible substrate can be produced by a method including: (a) preparing a resin sheet; or further, (b) laminating a plurality of resin composition layers using the resin sheet; and (c) curing the resin sheet or the laminated sheet.
[0287] In the manufacturing method of the flexible substrate, in combination with the above-mentioned steps, an optional step may be further included. For example, the manufacturing method of the flexible substrate with electronic components may further include the step of bonding the electronic components to the laminate. The bonding conditions of the laminate and the electronic components may adopt any conditions under which the terminal electrodes of the electronic components and the conductor layer as wiring provided on the laminate can be connected to each other. In addition, for example, the manufacturing method of the flexible substrate with a cover film may further include the step of laminating the laminate and the cover film.
[0288] The above-mentioned flexible substrate can usually be used by bending one surface of the laminated sheet included in the flexible substrate in a manner opposite to each other. For example, the flexible substrate is accommodated in a frame of a semiconductor device in a state of being bent and reduced in size. In addition, for example, in a semiconductor device having a bendable movable portion, the flexible substrate is provided on the movable portion.
[0289] [Semiconductor devices]
[0290] The semiconductor device includes the above-mentioned flexible substrate. The semiconductor device includes, for example, a flexible substrate and a semiconductor chip mounted on the flexible substrate. In many semiconductor devices, the flexible substrate can be folded so that one surface of the laminated sheet included in the flexible substrate faces each other and is accommodated in a housing of the semiconductor device.
[0291] Examples of the semiconductor device include various semiconductor devices provided for electrical products (eg, computers, mobile phones, digital cameras, and televisions) and vehicles (eg, motorcycles, cars, trains, ships, and airplanes).
[0292] The semiconductor device described above can be manufactured, for example, by a manufacturing method including the steps of: preparing a flexible substrate; bending the flexible substrate so that one surface of the laminated sheet faces the other; and housing the bent flexible substrate in a frame.
[0293] Example
[0294] The present invention is specifically described below by way of examples. The present invention is not limited to these examples. It should be noted that, unless otherwise indicated, "parts" indicating an amount refer to "parts by mass" below.
[0295] <Synthesis Example 1: Synthesis of Resin X1>
[0296] 112 g of difunctional hydroxy-terminated polybutadiene ("G-3000" manufactured by Nippon Soda Co., Ltd., number average molecular weight = 3000, hydroxyl equivalent = 1800 g / eq.), 272 g of anisole as a solvent and 14 g of isophorone diisocyanate (IPDI) were placed in a reaction container, the temperature was raised to 50°C, and the reaction was carried out for about 1 hour.
[0297] Next, 145 g of an oligophenylene ether resin containing phenolic hydroxyl groups at both ends (SA90-100 manufactured by Sabic, hydroxyl equivalent = 800 g / eq.) and 1 g of benzophenonetetracarboxylic dianhydride (BTDA) were added to the reactant, and the temperature was raised to 140° C. while stirring, and the reaction was carried out for about 4 hours. FT-IR was performed at 2250 cm -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was regarded as the end point of the reaction, and the reactants were cooled to room temperature. Then, the reactants were filtered with a 100-mesh filter cloth to obtain a resin X1 having a low-polyphenylene ether skeleton (non-volatile component 50% by mass, 25°C viscosity 6.0 Pa·s, weight average molecular weight 280,000, glass transition temperature 0°C).
[0298] <Synthesis Example 2: Synthesis of Resin X2>
[0299] 60 g of difunctional hydroxy-terminated polybutadiene ("G-1000" manufactured by Nippon Soda Co., Ltd., number average molecular weight = 1400, hydroxyl equivalent = 800 g / eq.), 220 g of anisole as a solvent and 14 g of isophorone diisocyanate (IPDI) were placed in a reaction container, the temperature was raised to 50°C, and the reaction was carried out for about 1 hour.
[0300] Next, 145 g of an oligophenylene ether resin containing phenolic hydroxyl groups at both ends (SA90-100 manufactured by Sabic, hydroxyl equivalent = 800 g / eq.) and 1 g of benzophenonetetracarboxylic dianhydride (BTDA) were added to the reactant, and the temperature was raised to 140° C. while stirring, and the reaction was carried out for about 4 hours. FT-IR was performed at 2250 cm -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was regarded as the end point of the reaction, and the reactants were cooled to room temperature. Then, the reactants were filtered with a 100-mesh filter cloth to obtain a resin X2 having a low-polyphenylene ether skeleton (non-volatile component 50% by mass, 25°C viscosity 2.0 Pa·s, weight average molecular weight 260,000, glass transition temperature 0°C).
[0301] <Synthesis Example 3: Synthesis of Resin X3>
[0302] 83 g of polycarbonate diol ("C-2015N" manufactured by Kuraray Co., Ltd., number average molecular weight = 2000, hydroxyl equivalent = 1000 g / eq.), 240 g of anisole as a solvent and 14 g of isophorone diisocyanate (IPDI) were placed in a reaction container, the temperature was raised to 50°C, and the reaction was carried out for about 1 hour.
[0303] Next, 145 g of an oligophenylene ether resin containing phenolic hydroxyl groups at both ends (SA90-100 manufactured by Sabic, hydroxyl equivalent = 800 g / eq.) and 1 g of benzophenonetetracarboxylic dianhydride (BTDA) were added to the reactant, and the temperature was raised to 140° C. while stirring, and the reaction was carried out for about 4 hours. FT-IR was performed at 2250 cm -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was regarded as the end point of the reaction, and the reactants were cooled to room temperature. Then, the reactants were filtered with a 100-mesh filter cloth to obtain a resin X3 having a low-polyphenylene ether skeleton (non-volatile component 50% by mass, 25°C viscosity 4.0 Pa·s, weight average molecular weight 254,000, glass transition temperature -4°C).
[0304] <Synthesis Example 4: Synthesis of Resin X'1>
[0305] 69 g of difunctional hydroxy-terminated polybutadiene ("G-3000" manufactured by Nippon Soda Co., Ltd., number average molecular weight = 3000, hydroxyl equivalent = 1800 g / eq.), 40 g of aromatic hydrocarbon mixed solvent ("Ipsol 150" manufactured by Idemitsu Petrochemical Co., Ltd.) and 0.005 g of dibutyltin laurate were placed in a reaction container and mixed to be uniformly dissolved. When the mixture became uniform, the temperature was raised to 60° C., and 8 g of isophorone diisocyanate ("IPDI" manufactured by Evonik Degussa Japan Co., Ltd., isocyanate equivalent = 113 g / eq.) was further added while stirring, and the reaction was carried out for about 3 hours.
[0306] Next, 23 g of cresol novolac resin ("KA-1160" manufactured by DIC Corporation, hydroxyl equivalent = 117 g / eq.) and 60 g of carbitol acetate (manufactured by Daicel Corporation) were added to the reactant, and the temperature was raised to 150° C. while stirring, and the reaction was carried out for about 10 hours. FT-IR was performed at 2250 cm -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was regarded as the end point of the reaction, and the reaction product was cooled to room temperature. Then, the reaction product was filtered with a 100-mesh filter cloth to obtain resin X'1 (phenolic hydroxyl-containing butadiene resin: non-volatile content 50% by mass, glass transition temperature -4°C).
[0307] <Synthesis Example 5: Synthesis of Maleimide A>
[0308] A MEK solution (non-volatile content 70% by mass) of maleimide A (n1 = 1.47, Mw / Mn = 1.81) represented by the following formula synthesized by the method described in Synthesis Example 1 of Japan Invention Association Publication No. 2020-500211 was obtained. In Example 10 described below, it was blended as a compound having a free radical polymerizable unsaturated group.
[0309] [Chemical formula 5]
[0310]
[0311] [Examples 1 to 11, Comparative Examples 1 to 2]
[0312] (1) Preparation of resin composition
[0313] According to the blending composition described in Table 1, each component was weighed, and 15 parts of MEK was further mixed, and the mixture was uniformly dispersed using a high-speed rotary mixer to obtain a resin composition (resin varnish).
[0314] (2) Manufacturing of resin sheets
[0315] As a support, a polyethylene terephthalate film ("AL5" manufactured by Lintec, 38 μm thick) having a release layer was prepared. The obtained resin varnish was evenly applied to the release layer of the support so that the thickness of the resin composition layer after drying was 50 μm. Thereafter, the resin composition was dried at 80°C to 120°C (average 100°C) for 4 minutes to obtain a resin sheet having a layer structure of a resin composition layer / support.
[0316] <Evaluation of elongation>
[0317] The resin sheets obtained in Examples and Comparative Examples were heated at 200° C. for 90 minutes to thermally cure the resin composition layer. Next, the support was peeled off to obtain a cured product of the resin composition layer.
[0318] The cured product was subjected to a tensile test using a Tensilon universal testing machine ("RTC-1250A" manufactured by ORIENTEC Corporation) in accordance with Japanese Industrial Standards (JIS K7127), and the elongation (%) at break at 23°C was measured.
[0319] <Evaluation of folding resistance by MIT test>
[0320] The resin sheets obtained in the examples and comparative examples were heated at 200° C. for 90 minutes to thermally cure the resin composition layer. The support was then peeled off to obtain a cured product of the resin composition layer. The cured product was cut into pieces with a width of 15 mm and a length of 110 mm to prepare test pieces for evaluation.
[0321] For each evaluation test piece, a MIT test device (manufactured by Toyo Seiki Seisaku-sho, MIT folding fatigue tester "MIT-DA") was used to perform a bending test under the measurement conditions of a load of 2.5N, a bending angle of 90 degrees, a bending radius of 1.0mm, and a bending speed of 175 times / minute in accordance with Japanese Industrial Standards (JIS C-5016). The number of folding times until the evaluation test piece broke was measured. It should be noted that the five test pieces were measured and the average of the first three points was calculated.
[0322] <Measurement of dielectric loss tangent>
[0323] The resin sheets obtained in the examples and comparative examples were heated at 200°C for 90 minutes to thermally cure the resin composition layer. The support was then peeled off to obtain a cured product of the resin composition layer. The cured product was cut into pieces with a width of 2 mm and a length of 80 mm to prepare test pieces for evaluation.
[0324] For each evaluation test piece, the dielectric loss tangent (Df value) was measured using the "HP8362B" manufactured by Agilent Technologies, using the cavity resonance perturbation method at a measurement frequency of 5.8 GHz and a measurement temperature of 23°C. The measurement was performed on three test pieces, and the average value was calculated. The obtained average value was evaluated according to the following criteria.
[0325] ×: Dielectric loss tangent is greater than 0.01;
[0326] ○: Dielectric loss tangent is less than 0.01.
[0327] <Evaluation of insulation reliability>
[0328] The resin sheets obtained in the examples and comparative examples are laminated on an imide film formed with a comb-shaped electrode (line / spacing = 15 μm / 15 μm) using an intermittent vacuum pressurizing laminator MVLP-500 (trade name, manufactured by Mingji Co., Ltd.) in such a manner that the resin composition layer of the resin sheet is in contact with the surface of the copper circuit. The lamination is performed by reducing the pressure for 30 seconds so that the air pressure is below 13 hPa, and then pressing at 100°C and a pressure of 0.74 MPa for 30 seconds. After the polyethylene terephthalate film of the support is peeled off, it is thermally cured at 200°C for 90 minutes to obtain a laminate for insulation reliability evaluation. The evaluation laminate is loaded into a highly accelerated life tester ("PM422" manufactured by Kusumoto Chemical Co., Ltd.), and the insulation resistance value of the evaluation laminate after 200 hours at 130°C, 85% RH, and a voltage of 3.3V is measured. The measured values are evaluated according to the following criteria.
[0329] ○: Insulation resistance value is 1.0×108 Ω or above;
[0330] ×: Insulation resistance value is less than 1.0×10 8 Ω.
[0331] <Evaluation of substrate adhesion>
[0332] (1) Base treatment of copper foil
[0333] The shiny surface of "3EC-III" (electric field copper foil, 35 μm) manufactured by Mitsui Mining and Smelting Co., Ltd. was immersed in MECetchBOND "CZ-8101" manufactured by MEC to roughen the copper surface (Ra value = 1 μm), and then rust-proof treatment (CL8300) was applied. This copper foil is called CZ copper foil. Furthermore, it was heated in an oven at 130°C for 30 minutes to obtain a CZ copper foil with a treated surface.
[0334] (2) Base treatment of inner substrate
[0335] A glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.8 mm, "R1515A" manufactured by Panasonic) with an inner layer circuit formed thereon was prepared. The laminate had copper foil as a conductor layer on the surface. Both sides of the laminate were immersed in MECetchBOND "CZ-8101" manufactured by MEC and etched by 1 μm to roughen the copper surface, thereby producing an inner layer substrate.
[0336] (3) Lamination of resin sheets
[0337] The resin composition layer of the resin sheet obtained in the examples and comparative examples was laminated on both sides of the inner substrate in a manner in contact with the inner substrate using an intermittent vacuum pressure laminator (manufactured by Nikko-Materials, 2-stage laminating laminator "CVP700"). The lamination process was carried out by reducing the pressure for 30 seconds to make the air pressure below 13 hPa, and then pressing at 120°C and a pressure of 0.74 MPa for 30 seconds. Then, hot pressing was performed at 100°C and a pressure of 0.5 MPa for 60 seconds. After that, the release PET as a support was peeled off to expose the resin composition layer.
[0338] (4) Copper foil lamination and insulation layer formation
[0339] The treated surface of CZ copper foil was laminated on the exposed resin composition layer, and the resin composition layer was cured under curing conditions of 200°C and 90 minutes to form a cured product (insulating layer), thereby producing a substrate having CZ copper foil laminated on both sides. The substrate was subjected to 10 heat treatments in a reflow soldering device ("HAS6116" manufactured by Antom, with a maximum reaching temperature of 260°C) to obtain an evaluation substrate.
[0340] (5) Measurement of copper foil peel strength (base adhesion)
[0341] The prepared evaluation substrate was cut into small pieces of 150 mm × 30 mm. A cutter was used to cut out a portion of 10 mm in width and 100 mm in length from the copper foil portion of the small piece. One end of the copper foil was peeled off and clamped with a clamp of a tensile tester (Autocom universal testing machine "AC-50C-SL" manufactured by TSE). The load (kgf / cm) when peeling off 35 mm in the vertical direction at a speed of 50 mm / min at room temperature (23°C) was measured according to Japanese Industrial Standards (JIS C6481), and the evaluation was performed according to the following criteria.
[0342] ×: The result of the measurement of the base adhesion is less than 0.4 kgf / cm;
[0343] ○: The measurement result of base adhesion is 0.4 kgf / cm or more.
[0344] Table 1 shows the results of Examples 1 to 11 and Comparative Examples 1 and 2.
[0345] [Table 1]
[0346]
[0347] In addition, the details of each component described in Table 1 are as follows.
[0348] <Thermosetting resin>
[0349] HP-4032D: naphthalene-based epoxy resin, functional group equivalent weight about 142 g / eq, manufactured by DIC Corporation;
[0350] YX7400N: flexible epoxy resin, functional group equivalent weight about 450g / eq, manufactured by Mitsubishi Chemical Corporation;
[0351] HP-7200: dicyclopentadiene type epoxy resin, functional group equivalent weight 259 g / eq, manufactured by DIC Corporation.
[0352] <Curing agent>
[0353] KA-1160: phenolic curing agent, cresol novolac resin, functional group equivalent 117g / eq, manufactured by DIC Corporation;
[0354] HPC-8000-65T: active ester curing agent, functional group equivalent 223 g / eq, toluene solution with non-volatile content 65% by mass, manufactured by DIC Corporation;
[0355] V-03: carbodiimide-based curing agent, functional group equivalent 216 g / eq, toluene solution containing 50% by mass of nonvolatile components, manufactured by Nisshinbo Chemical Co., Ltd.
[0356] <Resin X>
[0357] Resins X1 to X3: Resins X1 to X3 synthesized in Synthesis Examples 1 to 3, and anisole solutions containing 50% by mass of nonvolatile components.
[0358] <Resin X'>
[0359] Resin X'1: Resin X'1 synthesized in Synthesis Example 4, a solution containing 50% by mass of nonvolatile components.
[0360] <Curing accelerator>
[0361] ·1B2PZ: Imidazole derivative, manufactured by Shikoku Chemical Industry Co., Ltd.
[0362] <Compounds having a radically polymerizable unsaturated group>
[0363] BMI-689: a maleimide compound, manufactured by Designer Molecules Inc.
[0364] MIR-3000-70MT: Biphenyl aralkylphenol novolac type maleimide compound, a mixed solution of MEK solution and toluene with a non-volatile content of 70%, manufactured by Nippon Kayaku Co., Ltd.
[0365] ·L-DAIC: Allyl-containing resin, manufactured by Shikoku Chemical Industry Co., Ltd.
[0366] <Inorganic fillers>
[0367] SO-C2: Spherical silica surface-treated with an amino-based silane coupling agent ("KBM573" manufactured by Shin-Etsu Chemical Co., Ltd.), average particle size 0.5 μm, specific surface area 5.8 m 2 / g, manufactured by Admatechs.
Claims
1. A resin composition comprising a thermosetting resin, an inorganic filler, and a resin X having an oligophenylene ether skeleton and having a glass transition temperature of 25° C. or less, The cured product of the resin composition exhibits a dielectric loss tangent Df of less than 0.01 and satisfies at least one of the following conditions (1) and (2): (1) The elongation is 5% or more and less than 50%; (2) The number of folding times in the MIT folding test is 200 times or more.
2. The resin composition according to claim 1, wherein When the resin component in the resin composition is 100 mass %, the content of the resin X is 20 mass % or more and less than 85 mass %.
3. The resin composition according to claim 1, wherein When the non-volatile component in the resin composition is 100% by mass, the content of the inorganic filler is 50% by mass or less.
4. The resin composition according to claim 1, wherein The resin X contains one or more structural units selected from the group consisting of a polyolefin structural unit, a polycarbonate structural unit, a polyether structural unit, a polyester structural unit, a poly(meth)acrylic acid structural unit, and a polysiloxane structural unit.
5. The resin composition according to claim 1, wherein The resin X contains a cyclic imide structure. The resin composition according to claim 1 , which is used for forming an insulating layer of a flexible substrate.
7. A cured product of the resin composition according to any one of claims 1 to 6. 8 . A resin sheet comprising: a support and a layer of the resin composition according to claim 1 provided on the support.
9. The resin sheet according to claim 8, wherein The support is a thermoplastic resin film or a metal foil. 10 . A flexible substrate comprising an insulating layer composed of a cured product of the resin composition according to claim 1 .
11. A semiconductor device comprising the flexible substrate according to claim 10.
Citation Information
Patent Citations
Process for preparing butyl-p-benzoylbenzoates
EP0000502A1
Nitrogen-containing heterocyclic compounds as FXR modulators
JP2020500211A
